Zeolite material having a framework structure comprising Si, O and Ti

By using a titanium zeolite catalyst prepared with a Ti-containing compound with a APHA colorimetric ≤300, the problem of degradation of catalytic performance of the existing titanium zeolite catalyst in the epoxidation reaction is solved, and the epoxidation performance with high selectivity and stability is achieved.

CN115348950BActive Publication Date: 2025-01-10BASF SE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180023340.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-23
Filing Date
2021-03-22
Publication Date
2025-01-10
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

The existing titanium zeolite catalysts have problems of degradation in catalytic performance and weakening of selectivity in epoxidation reactions, especially due to the performance degradation caused by excessive APHA coloration of Ti-containing compounds.

Method used

A zeolite material with a framework structure including Si, O and Ti was prepared by using Ti-containing compounds with an APHA colorimeter ≤300. The selectivity and stability of the catalyst were improved by optimizing the synthesis method to avoid the formation of TiO2 and the destruction of alcoholates.

Benefits of technology

The selectivity and stability of the catalyst are significantly improved, especially the epoxidation performance of ≥85% during long-term operation, avoiding performance degradation at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003858742620000041
    Figure BDA0003858742620000041
  • Figure BDA0003858742620000042
    Figure BDA0003858742620000042
  • Figure BDA0003858742620000101
    Figure BDA0003858742620000101
Patent Text Reader

Abstract

The present invention relates to a zeolite material having a framework structure including Si, O and Ti obtained or obtainable from a Ti-containing compound, wherein the APHA color of the Ti-containing compound is ≤300. In a second aspect, the present invention relates to a Ti-containing compound having an APHA color of ≤300. In a third aspect, the present invention relates to the use of the Ti-containing compound having an APHA color of ≤300 of the second aspect for preparing a zeolite material having a framework structure including Si, O and Ti, and to a method for preparing a zeolite material having a framework structure including Si, O and Ti as in the first aspect, wherein the zeolite material having a framework structure including Si, O and Ti is prepared from the Ti-containing compound having an APHA color of ≤300 of the second aspect. In a fourth aspect, the present invention relates to a molded article comprising the zeolite material having a framework structure including Si, O and Ti of the first aspect, and to the use of the molded article as an adsorbent, absorbent, catalyst or catalyst component. In a fifth aspect, the present invention relates to a method for oxidizing an organic compound, comprising contacting the organic compound with a catalyst comprising the molded article of the fourth aspect, wherein the sixth aspect relates to propylene oxide obtained or obtainable by the method of the fifth aspect.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a zeolite material having a framework structure including Si, O and Ti obtained or obtainable from a Ti-containing compound, wherein the APHA color of the Ti-containing compound is ≤300. In a second aspect, the present invention relates to a Ti-containing compound having an APHA color of ≤300. In a third aspect, the present invention relates to the use of the Ti-containing compound having an APHA color of ≤300 of the second aspect for preparing a zeolite material having a framework structure including Si, O and Ti, and to a method for preparing a zeolite material having a framework structure including Si, O and Ti as in the first aspect, wherein the zeolite material having a framework structure including Si, O and Ti is prepared from the Ti-containing compound having an APHA color of ≤300 of the second aspect. In a fourth aspect, the present invention relates to a molded article comprising the zeolite material having a framework structure including Si, O and Ti of the first aspect, and to the use of the molded article as an adsorbent, absorbent, catalyst or catalyst component. In a fifth aspect, the present invention relates to a method for oxidizing an organic compound, comprising contacting the organic compound with a catalyst comprising the molded article of the fourth aspect, wherein the sixth aspect relates to propylene oxide obtained or obtainable by the method of the fifth aspect.

[0002] Propylene oxide is an important intermediate in the chemical industry. A suitable process for preparing propylene oxide starts with propylene, using hydroxide (H2O2) as an oxidant, a solvent and an epoxidation catalyst including a titanium zeolite. Useful titanium zeolites for this purpose include titanium silicate-1 (TS-1), which is a titanium silicate zeolite with an MFI framework structure. TS-1 has attracted widespread attention due to its ability to undergo clean oxidation reactions under relatively mild conditions. TS-1 is usually hydrothermally synthesized using a Ti-containing alcoholate (alkoxide) precursor to achieve controlled incorporation of Ti into the zeolite framework. As a choice of Ti precursor, compounds such as tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) or tetra-n-butyl orthotitanate Ti(OBu)4 are often used. It is known that TS-1 obtained by a common preparation method does not contain all Ti as a framework element due to its strong tendency to polymerize under aqueous conditions, but part of the Ti exists as extra-framework Ti, for example, in the form of titanium dioxide (anatas form).

[0003] US 2013 / 296159 A1 describes a process for preparing zeolitic materials, in which, inter alia, tetraethyl orthotitanate (TEOTi, Ti(OEt) 4 ) is used as a titanium source; EP 0 712 852 A1 relates to a process for the epoxidation of olefins using a TS-1 catalyst.

[0004] D.-G. Huang et al. (Deng-Gao Huang, Xian Zhang, Bao-Hui Chen, Zi-Sheng Chao, Catalysis Today, 158 (2010), pp. 510-514) describe the preparation of TS-1 by three different methods, using tetraethyl orthosilicate and tetrabutyl orthotitanate as Si and Ti sources, and tetrapropylammonium hydroxide as a template. The positive effect of alcohols (e.g., ethanol) on the synthesis is described, where slow hydrolysis of Ti-containing species and reduced formation of titanium dioxide (anatase form) are shown. Indian published patent application IN 189381 A discloses that ketones can be used to stabilize Ti-containing species and can be used to prevent anatase formation. That is, the prior art seems to indicate that the presence of alcohols and ketones will be beneficial to TS-1 synthesis.

[0005] Due to the importance of products such as propylene oxide in industry, it is desirable to carry out the epoxidation of propylene as efficiently as possible, including optimizing the catalyst used as much as possible. Therefore, the object of the present invention is to provide a zeolitic material having a framework structure comprising Si, O and Ti, which is economically advantageous as a catalyst in the preparation of propylene oxide.

[0006] Ti-containing compounds, such as Ti(OEt)4, are usually described as colorless liquids, but these compounds tend to develop color over time. It has now been surprisingly found that the color of the Ti-containing compound is very important for the properties of the final zeolite material having a framework structure comprising Si, O and Ti prepared therefrom.

[0007] First aspect - zeolite material having a framework structure comprising Si, O and Ti

[0008] Therefore, a first aspect of the present application relates to a zeolitic material having a framework structure comprising Si, O and Ti, obtained or obtainable from a Ti-containing compound, wherein the Ti-containing compound has an APHA color of ≤300.

[0009] In the context of the present invention, the APHA color is determined in accordance with DIN EN ISO 6271: 2016-05. An APHA color of the Ti-containing compound of ≤ 300 means that preferably the APHA color is in the range of 0 (zero) to 300. More preferably, the APHA chromaticity is ≤290 (in the range of 0 to 290), more preferably the APHA chromaticity is ≤280 (in the range of 0 to 280), more preferably the APHA chromaticity is ≤270 (in the range of 0 to 270), more preferably the APHA chromaticity is ≤260 (in the range of 0 to 260), more preferably the APHA chromaticity is ≤251 (in the range of 0 to 251), more preferably the APHA chromaticity is ≤250 (in the range of 0 to 250), more preferably the APHA chromaticity is ≤200 (in the range of 0 to 200), more preferably the APHA chromaticity is ≤150 (in the range of 0 to 150), more preferably the APHA chromaticity is ≤105 (in the range of 0 to 105).

[0010] It has surprisingly been found that when zeolitic materials having a framework structure comprising Si, O and Ti obtained or obtainable from Ti-containing compounds, wherein the titanium-containing compound has an APHA color of ≤300, are used as catalysts for the (preferably continuous) epoxidation of C2 to C5 olefins with hydrogen peroxide, the catalytic performance, in particular the selectivity, decreases with increasing APHA number of the Ti-containing compound used to synthesize the zeolitic material. At APHA numbers above 300, higher temperatures in the epoxidation zone (and thus higher temperatures of the cooling medium) are required in order to keep the hydrogen peroxide conversion at a value comparable to that when the Ti-containing compound used to synthesize the zeolitic material has an APHA number of ≤300. However, when these zeolitic materials based on Ti-containing compounds having such high APHA numbers are used as catalysts, the selectivity is very poor, i.e. <85%, even at higher temperatures. For example, in the epoxidation of propylene with hydrogen peroxide, the selectivity of propylene oxide relative to hydrogen peroxide (S(H2O2) to PO) can be significantly increased relative to hydrogen peroxide. Even though the different catalysts appear comparable during the initial run, it can be seen that at longer run times, such as >150 h, preferably >200 h, more preferably >250 h, the catalyst based on a Ti-containing compound with an APHA color of ≤300 achieves a significantly higher selectivity of ≥85% (ranging from 85% to 95%). The catalyst based on a Ti-containing compound with an APHA color of >300 results in a selectivity of <85% at longer run times.

[0011] The zeolite material having a framework structure including Si, O and Ti is obtained or obtainable from the above-mentioned Ti-containing compound. Preferably, the Ti-containing compound includes a Ti-containing alcoholate (alkoxide), preferably selected from Ti(O-alkyl)4, wherein each alkyl group is independently selected from a branched or unbranched C1 to C6 alkyl group; more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds; more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

[0012] Preferably, the Ti-containing compound from which the zeolitic material having a framework structure comprising Si, O and Ti is obtained or obtainable comprises at least 90 wt.-%, preferably at least 95 wt.-%, more preferably at least 96 wt.-%, more preferably at least 97 wt.-%, more preferably at least 98 wt.-%, more preferably at least 99 wt.-% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound. "At least 90 wt.-%" means a value in the range of 90 to 100 wt.-%; the same applies to the other values ​​mentioned above.

[0013] Preferably, the Ti-containing compound from which the zeolitic material having a framework structure comprising Si, O and Ti is obtained or obtainable comprises ≤ 10 wt. %, more preferably ≤ 5 wt. %, more preferably ≤ 4 wt. %, more preferably ≤ 3 wt. %, more preferably ≤ 2 wt. %, more preferably ≤ 1 wt. % of a substance of formula (I), based on the total weight of the Ti-containing compound,

[0014]

[0015] Among them, R 1 and R 2 are independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups, R 3 Selected from hydrogen atoms, branched or unbranched C1 to C6 alkyl groups and branched or unbranched C1 to C6 alkenyl groups. "≤10 wt%" means that the value is in the range of 0 (zero) to 10 wt%; the same applies to the other values ​​mentioned above.

[0016] The substances of formula (I) may be present in the form of monomers as shown in formula (I) or in the form of oligomers having 2 to 7 repeating units. These oligomers are present only in an amount of <100 ppm, preferably <50 ppm, more preferably <10 ppm, based on the total weight of the Ti-containing compound. In addition to one or more substances of formula (I), the Ti-containing compound may include an isophorone-based substance of formula (II),

[0017]

[0018] Where R 4 , R 5 and R 6 Independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups. The substance of formula (I) is preferably selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-diene-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone, 2,6-dimethyl-hept-2,5-diene-4-one) and a mixture of hept-2,5-diene-4-one and 2,6-dimethyl-hept-2,5-diene-4-one. In an embodiment in which the Ti-containing compound comprises Ti(OEt)4, the substance of formula (I) includes at least CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-diene-4-one). In embodiments where the Ti-containing compound comprises Ti(OPr)4, the material of formula (I) includes at least (CH3)2C=CH-C(=O)-CH=C(CH3)2(2,6-dimethyl-hepta-2,5-dien-4-one).

[0019] As mentioned above, it was unexpectedly found that when zeolitic materials are used as catalysts for the (preferably continuous) epoxidation of C2 to C5 olefins with hydrogen peroxide, the catalytic performance, in particular the selectivity, decreases with increasing APHA number of the titanium-containing compound used to synthesize the zeolitic material. It can therefore be concluded that coloring of Ti-containing compounds including Ti-containing alcoholates (APHA color number ≤ 300, determined according to DIN EN ISO 6271:2016-05) should be avoided in the synthesis of zeolitic materials. Without being bound by theory, it is assumed that residual amounts of water in the Ti-containing compounds including Ti-containing alcoholates lead to the destruction of the alcoholates and the formation of TiO2. The TiO2, which can be detected in the final zeolitic material, appears to act as a photosensitizer and catalyzes the oxidation of the remaining alcoholates, such as isopropanolates or ethanolates, to the corresponding carbonyl (C=O)-containing compounds (aldehydes or ketones). Carbonyl-containing compounds, such as acetaldehyde or acetone, undergo aldol condensation under strongly alkaline conditions, wherein the resulting aldol condensation product corresponds to formula (I). These aldol condensation products contribute to color and interfere with the synthesis of zeolitic materials having a framework structure comprising Si, O and Ti.

[0020] The zeolite material obtained or obtainable from the above-mentioned Ti-containing compound and having a framework structure comprising Si, O and Ti preferably has a titanium dioxide content of ≤1.5 wt.%, preferably ≤1.2 wt.%, more preferably ≤1 wt.%, more preferably ≤0.5 wt.%, based on the total weight of the zeolite material, wherein preferably at least 98 wt.% of the titanium dioxide is in the form of anatase, as determined according to Reference Example 7.

[0021] The zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from the above Ti-containing compound preferably has a crystallinity of more than 85 wt%, preferably between 85 and 95 wt%, more preferably between 87 and 93 wt%, based on the total weight of the zeolitic material, as determined according to Reference Example 7. The zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from the above Ti-containing compound preferably exhibits a propylene oxide activity of at least 8.5 wt%, more preferably between 8.5 and 9.5 wt%, more preferably between 8.5 and 9.0 wt%, as determined as described in Reference Example 1. Preferably, the zeolitic material exhibits a propylene oxide activity of 440 to 580 m / s as determined as described in Reference Example 4. 2 / g, preferably 450 to 570m 2 / g BET specific surface area.

[0022] Preferably, 95 to 100 wt.-%, preferably 98 to 100 wt.-%, more preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the zeolitic material obtained or obtainable from the above-mentioned Ti-containing compound consists of Si, O, Ti and optionally H. Preferably, the zeolitic material comprises Ti in an amount of 0.2 to 5 wt.-%, more preferably 0.5 to 4 wt.-%, more preferably 1.0 to 3 wt.-%, more preferably 1.2 to 2.5 wt.-%, more preferably 1.4 to 2.2 wt.-%, calculated as elemental Ti and based on the total weight of the zeolitic material.

[0023] Preferably, the zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from the above Ti-containing compound is a zeolitic material having ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, CDO, CFI, CGF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EMT, EPI, ERI, ESV, ETR, EUO, FAU, FER, FRA, GIS, GIU, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, GON, GME, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, CDO, CFI, CGF, CGS, CHA, CHI, CLO, CON, CZP, OO, HEU, IFR, ISV, ITE, ITH, ITQ, ITW, IWR, IWW, JBW, KFI, LAU, LEV, LIO, LOS, LOV, LTA, LTL, LTN , MAR, MAZ, MCM-22(S), MCM-36, MCM-56, MEI, MEL, MEP, MER, MIT-1, MMFI, MFS, MON, MOR, MSE, MSO , MTF, MTN, MTT, MTW, MWW, NAB, NAT, NEES, NON, NPO, OBW, OFF, OSI, OSO, PAR, PAU, PHI, PON, RHO, RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN SFO, SGT, SOD, SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, VFI, VNI, VSV, WEI, WEN, YUG, ZON SVR, SVY framework structure or a titanium zeolite of a mixed structure of two or more of these framework types; more preferably, the zeolite material having a framework structure comprising Si, O and Ti is a titanium zeolite having an MFI framework type, a MEL framework type, an MWW framework type, an MCM-22 (S) framework type, an MCM-56 framework type, an IEZ-MWW framework type, an MCM-36 framework type, an ITQ framework type, a BEA framework type, a MOR framework type or a mixed structure of two or more of these framework types; more preferably, an MFI framework type or an MWW framework type; more preferably, the zeolite material having a framework structure comprising Si, O and Ti has a framework type MFI;More preferably, the zeolite material having a framework structure comprising Si, O and Ti is titanium silicalite-1 (TS-1). Framework types such as MCM-22 (S), MCM-56, IEZ-MWW, ITQ (layered MWW), MIT-1 and MCM-36 are titanium zeolites having a framework structure relative to the MWW framework structure, obtained or obtainable therefrom or obtained or obtainable from two separate spatial precursors by, for example, layer expansion and / or post-modification. ;

[0024] There is no limitation on how to prepare the zeolitic material having a framework structure comprising Si, O and Ti from the Ti-containing compound, as long as the zeolitic material is finally obtained. Suitable methods for such synthesis are known to those skilled in the art, including the generally known hydrothermal synthesis method.

[0025] In some embodiments, a zeolite material having a framework structure comprising Si, O and Ti is prepared from one or more Si sources, one or more Ti-containing compounds and one or more structure directing agents. These compounds are mixed in a suitable manner in the presence of water to obtain an aqueous mixture, which is then crystallized at elevated temperature and elevated pressure.

[0026] Si Source

[0027] Preferably, the one or more Si sources include one or more compounds selected from silica, silicates, silicates and mixtures thereof; preferably selected from fumed silica, silica hydrosol, reactive amorphous solid silica, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicate, disilicate, colloidal silica, pyrogenic silica, silicate, tetraalkoxysilane, and mixtures of two or more thereof; more preferably, silica hydrosol, silica gel, water glass, sodium metasilicate hydrate, colloidal silica, silicate, tetraalkoxysilane, and mixtures of two or more thereof; more preferably, silica hydrosol, silicic acid, colloidal silica, silicate, tetraalkoxysilane and mixtures of two or more thereof; wherein more preferably Preferably, the one or more Si sources include one or more tetraalkoxysilanes selected from (C1-C6)tetraalkoxysilane and mixtures of two or more thereof; preferably (C1-C5)tetraalkoxysilane and mixtures of two or more thereof; more preferably (C1-C4)tetraalkoxysilane and mixtures of two or more thereof; more preferably (C1-C3)tetraalkoxysilane and mixtures of two or more thereof; wherein more preferably the one or more Si sources include tetramethoxysilane and / or tetraethoxysilane, preferably tetraethoxysilane; and wherein more preferably the one or more Si sources are tetramethoxysilane and / or tetraethoxysilane, preferably tetraethoxysilane (tetraethyl orthosilicate).

[0028] Structure directing agent

[0029] Preferably, the one or more structure directing agents include one or more compounds selected from amines, quaternary ammonium compounds, alcohols, and mixtures of two or more of these agents. Preferably, the one or more structure directing agents are selected from tetraalkylammonium cations R 1 R 2 R 3 R 4 N + A compound wherein R 1 , R 2 , R 3 and R 4 Each independently represents a C1 to C10 alkyl group. 1 , R 2 , R 3 and R 4 Each independently represents a (optionally branched) C1-C6 alkyl group, preferably a C1-C5 alkyl group, more preferably a C2-C4 alkyl group, more preferably a (optionally branched) C2-C3 alkyl group, wherein R 1, R 2 , R 3 and R 4 Each independently represents an ethyl group or a propyl group, wherein R 1 , R 2 , R 3 and R 4 All represent propyl groups, preferably n-propyl groups.

[0030] Preferably, one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The compounds are independently salts, more preferably one or more salts selected from halides, preferably chlorides and / or bromides, more preferably chlorides, hydroxides, sulfates, nitrates, phosphates, acetates and mixtures of two or more thereof, more preferably selected from chlorides, hydroxides, sulfates and mixtures of two or more thereof, wherein more preferably one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The compound is tetraalkylammonium hydroxide and / or tetraalkylammonium chloride, more preferably tetraalkylammonium hydroxide. The one or more structure directing agents are preferably used in the form of an aqueous solution.

[0031] For details of the one or more Ti-containing compounds, reference is made to the second aspect described below. As described in more detail below, the one or more Ti-containing compounds are Ti-containing compounds having an APHA color number ≤300.

[0032] In some embodiments, the method of preparing a zeolite material having a framework structure comprising Si, O, and Ti comprises:

[0033] a) preparing a mixture comprising one or more Si sources, one or more Ti-containing compounds, one or more structure directing agents and water;

[0034] b) feeding the mixture prepared in (a) into a reactor; and

[0035] c) crystallizing a zeolitic material having a framework structure comprising Si, O and Ti from the mixture in a reactor, wherein the mixture is heated to a temperature of 70 to 300°C.

[0036] There is no limitation on how and in what order the one or more Si sources, one or more Ti-containing compounds, one or more structure directing agents, and water are mixed.

[0037] In some embodiments, it is preferred that the one or more Ti-containing compounds and the one or more structure directing agents in aqueous solution are premixed prior to step a), preferably in a closed container, and the alcohol formed is subsequently removed by distillation to obtain an aqueous solution comprising the reaction product of the one or more Ti-containing compounds and the one or more structure directing agents. For example, if tetraethyl orthotitanate (Ti(OEt)4) is used as the Ti-containing compound and an aqueous solution of tetrapropylammonium hydroxide is used as the structure directing agent, the reaction product is an aqueous solution of titanium-tetrapropylammonium hydroxide.

[0038] In the case of premixing, a zeolite material having a framework structure comprising Si, O and Ti is prepared by the following method, the method comprising:

[0039] a') preparing a mixture comprising one or more Si sources, a reaction product from premixing one or more Ti-containing compounds and one or more structure directing agents, and water;

[0040] b) feeding the mixture prepared in (a') into a reactor; and

[0041] c) crystallizing a zeolitic material having a framework structure comprising Si, O and Ti from the mixture in a reactor, wherein the mixture is heated to a temperature of 70 to 300°C.

[0042] Preferably, the reactors of b) and c) are pressure-resistant, such as autoclaves.

[0043] The process is carried out in batch mode (batch mode) or continuously (continuous mode). Preferably, for the continuous mode, at least one of the preferred steps a), b and c), at least one of the steps a'), b and c), respectively, is carried out continuously. More preferably, for the continuous mode, all steps a), b) and c), and a'), b) and c), respectively, are carried out continuously. For the continuous process, it is preferred to use a continuous flow reactor as the reactor for b) and c).

[0044] The H2O:Si molar ratio of water to one or more Si sources (calculated as SiO2) in the mixtures prepared in (a) and (a') is preferably 100:1 to 10:1, respectively. Preferably, the Si:Ti molar ratio of one or more Si sources (calculated as SiO2) to one or more Ti-containing compounds (calculated as TiO2) in the mixtures prepared in (a) and (a') is 1:100 to 100:1, more preferably 1:50 to 50:1, more preferably 10:1 to 50:1. The molar ratio of one or more structure directing agents to one or more titanium-containing compounds (calculated as TiO2) in the mixtures prepared in (a) and (a') is preferably 5:1 to 100:1, more preferably from 10:1 to 50:1, more preferably 20:1 to 40:1, respectively.

[0045] Preferably, step c) is carried out at a temperature of 90 to 280° C., more preferably 110 to 250° C., more preferably 130 to 220° C., more preferably 150 to 200° C., more preferably 160 to 190° C., more preferably 170 to 180° C. Preferably, step c) is carried out at autogenous pressure, wherein the preferred pressure is 0.5 to 15 MPa, more preferably 1 to 12 MPa, more preferably 1.5 to 11 MPa, more preferably 2 to 10 MPa. Here and below, the unit bar refers to bar (abs), which refers to 10 5 Absolute pressure of pa (1 bar = 10 5 pa).

[0046] Preferably, before b), the mixture prepared in a) is aged at a temperature of 15 to 120° C., more preferably 20 to 115° C., more preferably 22 to 100° C. Preferably, the aging is carried out over a period of 0.05 to 48 hours, more preferably 0.15 to 24 hours, more preferably 0.25 to 12 hours, more preferably 0.5 to 6 hours, more preferably 0.75 to 3 hours, more preferably 1 to 2 hours. The alcohol formed during the aging is preferably at least partially removed by distillation.

[0047] The method may include further method steps. Preferably, the method further includes

[0048] d) treating the reaction product effluent leaving the reactor in c) with a liquid comprising one or more solvents and / or by expansion of the reaction product effluent;

[0049] and / or, preferably and,

[0050] e) isolating the zeolitic material obtained in c) or d);

[0051] f) optionally washing the zeolitic material obtained in c), d) or f);

[0052] g) drying the zeolitic material obtained in c), d), e) or f);

[0053] and / or, preferably and,

[0054] h) calcining the zeolitic material obtained in c, d), e), f) or g).

[0055] In case the process comprises g), the drying in g) is preferably carried out at a temperature of 50 to 220° C., preferably 70 to 190° C., more preferably 80 to 170° C., more preferably 90 to 150° C., more preferably 100 to 140° C., more preferably 110 to 130° C., preferably for 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 6 hours.

[0056] In the case where the process includes h), the calcination in h) is preferably carried out at a temperature of 300 to 700° C., more preferably 375 to 625° C., more preferably 425 to 575° C., more preferably 470 to 550° C. As to the duration of the calcination, there is no limitation, as long as the final calcined material obtained by h) has a suitable three-dimensional zeolite structure, which can be easily determined by a person skilled in the art, for example, by measurement and analysis of X-ray diffraction (XRD) data. For example, in the case of a batch process, the calcination is preferably carried out for a period of 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 6 hours.

[0057] Aspect 2 - Ti-containing compounds with APHA chromaticity ≤ 300

[0058] In a second aspect, the present invention relates to a Ti-containing compound having an APHA color number ≤ 300. Preferably, the Ti-containing compound comprises a Ti-containing alcoholate, preferably selected from Ti(O-alkyl)4, wherein each alkyl group is independently selected from branched or unbranched C1 to C6 alkyl groups, more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds, more preferably tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

[0059] Preferably, the Ti-containing compound having an APHA color of ≤300 comprises at least 90 wt. %, preferably at least 95 wt. %, more preferably at least 96 wt. %, more preferably at least 97 wt. %, more preferably at least 98 wt. %, more preferably at least 99 wt. % of titanium-containing alcoholate, based on the total weight of the titanium-containing compound. The Ti-containing compound preferably comprises ≤10 wt. %, more preferably ≤5 wt. %, more preferably ≤4 wt. %, more preferably ≤3 wt. %, more preferably ≤2 wt. %, more preferably ≤1 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

[0060]

[0061] Among them, R 1 and R 2R is independently selected from hydrogen atom and branched or unbranched C1 to C6 alkyl, and R3 is selected from hydrogen atom, branched or unbranched C1 to C6 alkyl and branched or unbranched C1 to C6 alkenyl. The substance of formula (I) is preferably selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-diene-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone=2,6-dimethyl-hept-2,5-diene-4-one) and a mixture of hept-2,5-diene-4-one and 2,6-dimethyl-hept-2,5-diene-4-one.

[0062] Aspect 3 - Use of Ti-containing compounds

[0063] In a third aspect, the present invention relates to the use of the above-mentioned Ti-containing compound with an APHA color number of ≤300 in the second aspect in the preparation of the zeolite material having a framework structure comprising Si, O and Ti in the first aspect. Therefore, the present invention also relates to a method for preparing a zeolite material having a framework structure comprising Si, O and Ti, wherein the zeolite material having a framework structure comprising Si, O and Ti is prepared from the Ti-containing compound with an APHA color number of ≤300, wherein the Ti-containing compound is as described in the second aspect.

[0064] Aspect 4 – Molded Products

[0065] The present invention also relates in a fourth aspect to a molded article comprising the zeolite material having a framework structure comprising Si, O and Ti according to the above-mentioned first aspect.

[0066] Preferably, the molding exhibits a tortuosity parameter of <4, more preferably 1.0 to 2.5, more preferably 1.3 to 2.0, more preferably 1.40 to 1.80, more preferably 1.50 to 1.75, more preferably 1.55 to 1.70 relative to water, determined as described in Reference Example 5. The pore volume of the molding, determined according to DIN 66133: 1993-06, is preferably from 0.1 to 1.5 ml / g.

[0067] According to a further fourth aspect, the present invention also relates to a molded article as an adsorbent, an absorbent, a catalyst or a catalyst component, preferably as a catalyst or as a catalyst component, more preferably as a Lewis acid catalyst or a Lewis acid catalyst component, as an isomerization catalyst or as an isomerization catalyst component, as an oxidation catalyst or as an oxidation catalyst component, as an aldol condensation catalyst or as an aldol condensation catalyst component, or as a Prins reaction catalyst or as a Prins reaction catalyst component.

[0068] With regard to the use as an oxidation catalyst or oxidation catalyst component, the molded article is preferably used as an epoxidation catalyst or as an epoxidation catalyst component, more preferably as an epoxidation catalyst. Preferably, the molded article is used for the epoxidation of an organic compound having at least one C-C double bond, preferably a C2-C10 olefin, more preferably a C2-C5 olefin, more preferably a C2-C4 olefin, more preferably a C2 or C3 olefin, more preferably propylene, more preferably for the epoxidation of propylene with hydrogen peroxide as oxidant, more preferably for the epoxidation of propylene with hydrogen peroxide as oxidant in a solvent comprising an alcohol, preferably methanol.

[0069] Fifth Aspect - Method for Oxidizing Organic Compounds

[0070] In a fifth aspect, the present invention relates to a process for oxidizing an organic compound, comprising contacting the organic compound with a catalyst (preferably in a continuous manner), the catalyst comprising the molding according to the fourth aspect, preferably for epoxidizing an organic compound, more preferably for epoxidizing an organic compound having at least one C-C double bond, preferably a C2-C10 olefin, more preferably a C2-C5 olefin, more preferably a C2-C4 olefin, more preferably a C2 or C3 olefin, more preferably propylene. Preferably hydrogen peroxide is used as the oxidant, wherein the (ep)oxidation reaction is preferably carried out in a solvent, more preferably in a solvent comprising an alcohol (preferably methanol). More preferably, the (ep)oxidation reaction is carried out in a solvent mixture comprising a solvent and water, more preferably in a solvent mixture comprising an alcohol (preferably methanol) and water.

[0071] Furthermore, according to a fifth aspect, the present invention relates to a process for preparing propylene oxide, which comprises reacting propylene with hydrogen peroxide in a solvent, preferably in a continuous manner, in the presence of a catalyst comprising a molded article according to the fourth aspect, to obtain propylene oxide. The reaction of propylene with hydrogen peroxide in a solvent in the presence of a catalyst is preferably carried out in an epoxidation zone, the absolute pressure in the epoxidation zone being 0.5 to 5.0 MPa, preferably 1.5 to 3.0 MPa, more preferably 1.8 to 2.8 MPa.

[0072] Preferably, the reaction of propene with hydrogen peroxide in a solvent in the presence of a catalyst is carried out in the epoxidation zone at a temperature of 33 to 73° C., preferably 38 to 63° C., more preferably 53 to 63° C. The temperature in the epoxidation zone is measured with ten times the thermocouples, i.e. ten thermocouples. The epoxidation zone is defined as the zone in which the reaction of hydrogen peroxide and propene to give propylene oxide still takes place in detectable amounts (≥10 ppm propylene oxide). Preferably, the epoxidation zone is present over the entire length of the catalyst bed, i.e. the epoxidation zone, preferably within the reactor, is the zone in which the epoxidation catalyst is present (epoxidation zone=catalyst bed). The hotspot, i.e. the zone in which the maximum reaction takes place, is generally located in the first half of the catalyst bed, preferably ≥ six of the ten thermocouples are located in the first half of the catalyst bed.

[0073] The temperature in the epoxidation zone is the average temperature determined by the temperature values ​​measured by all thermocouples located in the front half of the catalyst bed. Typically, the temperature values ​​measured by these thermocouples differ from each other within the range of 6 to 10°C.

[0074] Preferably, a cooling medium is used to adjust the temperature of the epoxidation zone, wherein the temperature of the cooling medium is preferably in the range of 25 to 65°C, preferably in the range of 30 to 55°C, more preferably in the range of 345 to 55°C. The temperature of the cooling medium is preferably the temperature of the cooling medium at the reactor inlet. A temperature of the cooling medium of 45 to 55°C is an optimum temperature range. Temperatures below 45°C are associated with the start-up phase of the epoxidation reaction and are too low for effective conditioning during the epoxidation reaction. Above 55°C, the decomposition of hydrogen peroxide and the formation of oxygen increase exponentially. Within the range of 45 to 55°C of the cooling medium, the temperature of the epoxidation zone is in the optimum range of 53 to 63°C, thereby achieving maximum selectivity and optimum activity.

[0075] In the process for preparing propylene oxide, the weight ratio (w / w) of propylene:hydrogen peroxide is preferably from 1:1 to 6:1, more preferably from 1:1 to 2:1 or from 4:1 to 5:1. The weight ratio (w / w) of solvent:hydrogen peroxide is preferably from 15:1 to 5:1, more preferably from 12:1 to 6:1, more preferably from 11:1 to 8:1. The weight ratio (w / w) of solvent:propylene in the reaction mixture is from 10:1 to 1:0.1, preferably from 9:1 to 1:1, more preferably from 9:1 to 7:1 or from 1.5:1 to 1:1.

[0076] The solvent is preferably an organic solvent, more preferably an organic epoxidation solvent, more preferably the organic solvent is selected from alcohol, acetonitrile, tert-butyl alcohol, propionitrile and a mixture of two or more thereof; more preferably selected from alcohol, acetonitrile and a mixture of alcohol and acetonitrile; more preferably the organic solvent comprises at least one alcohol. "The organic solvent comprises at least one alcohol" means that at least 90% by weight, preferably at least 95% by weight, more preferably at least 98% by weight, more preferably at least 99% by weight of the organic solvent consists of alcohol, based on the total weight of the organic solvent. The alcohol is preferably a C1 to C5 monohydric alcohol or a mixture of two or more C1 to C5 alcohols, more preferably the alcohol comprises at least methanol, more preferably the alcohol is methanol. According to a preferred embodiment, the organic solvent is methanol.

[0077] There are no restrictions on the water used for the solvent mixture. For example, water treated with NH3 can be considered, but water not treated with NH3 can also be used. Deionized water is preferably used for the reaction mixture. Deionized water can be obtained by using an ion exchanger of condensed water. Typical grades of deionized water are defined in ISO 3696 from 1987, and all grades described therein can be used within the scope of the present invention. The water may also contain traces of corrosion-inhibiting additives, such as ammonia, hydrazine or hydroxylamine, in which case its pH value should be between 7 and 9 (measured using a calibrated glass electrode). Preferably, the water used does not contain corrosion-inhibiting additives.

[0078] Typically, the so-called "reaction mixture" comprises propylene, water, an organic solvent and hydrogen peroxide and can be provided according to any possible method. Preferably, the reaction mixture comprising propylene, water, an organic solvent and hydrogen peroxide or a source of hydrogen peroxide is prepared from two or more streams. More preferably, the reaction mixture is provided by combining at least three separate streams, wherein the first stream comprises hydrogen peroxide or a source of hydrogen peroxide, optionally as an aqueous solution, the second stream comprises propylene and optionally propane, and the third stream comprises an organic solvent and optionally water.

[0079] Generally, it is contemplated that pure or substantially pure propylene is used as a starting material and as a part of a reaction mixture. A mixture of propylene and propane is preferably used. Most preferably, the industrial propylene grade according to international standards such as ASTM D5273 or DIN 51622 is used. If a mixture of propylene and propane is used, the weight ratio of propylene: propane is preferably at least 7:3. For example, commercially available propylene can be used, which can be polymer grade propylene or chemical grade propylene. Generally, the propylene content of polymer grade propylene is 99 to 99.8 weight %, and the propane content is 0.2 to 1 weight %. The propylene content of chemical grade propylene is generally 92 to 98 weight %, and the propane content is 2 to 8 weight %. According to a preferred embodiment of the present invention, a mixture of propylene and propane is used, and its propylene content is 99 to 99.8 weight %, and the propane content is 0.2 to 1 weight %.

[0080] Preferably, hydrogen peroxide is used in the form of an aqueous hydrogen peroxide solution. The total organic carbon content (TOC) of the aqueous hydrogen peroxide solution is preferably 100 to 800 mg / kg of hydrogen peroxide contained in the aqueous hydrogen peroxide solution, more preferably 120 to 750 mg / kg of hydrogen peroxide contained in the aqueous hydrogen peroxide solution, more preferably 150 to 700 mg / kg of hydrogen peroxide contained in the aqueous hydrogen peroxide solution, determined according to DIN EN 1484.

[0081] In general, there is no particular limitation on the pH of the aqueous hydrogen peroxide solution and the amount of hydrogen peroxide contained in the solution, as long as the epoxidation of propylene can be effectively carried out. Preferably, the pH of the aqueous hydrogen peroxide solution is 0 to 3.0, more preferably 0.1 to 2.5, more preferably 0.5 to 2.3, as measured in Reference Example 4. The hydrogen peroxide solution contains 20 to 80% by weight, preferably 30 to 70% by weight, more preferably 40 to 60% by weight of hydrogen peroxide relative to the total weight of the aqueous hydrogen peroxide solution. In general, there is no particular limitation on the source of the aqueous hydrogen peroxide solution, as long as the epoxidation of propylene can be effectively carried out. Preferably, the aqueous hydrogen peroxide solution is obtained or obtainable by the anthraquinone process.

[0082] According to one embodiment of the present invention, it is preferred to use an aqueous hydrogen peroxide solution which is obtained as a crude hydrogen peroxide solution by extracting a mixture produced by a process known as the anthraquinone process (see, for example, Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, volume A 13 (1989) pages 443-466), wherein an anthraquinone solution containing an alkyl group preferably having 2 to 10 carbon atoms, more preferably having 2 to 6 carbon atoms, more preferably having preferably 2, 5 or 6 carbon atoms is used, and wherein the solvent used generally consists of a mixture of at least two different solvents. Preferably, a mixture of two solvents or a mixture of three solvents is used. Preferably, none of the solvents used in the anthraquinone process is a nitrogen-containing substance. Such anthraquinone solutions are generally referred to as working solutions. In this process, the hydrogen peroxide formed during the anthraquinone process is generally separated from the corresponding working solution by extraction after a hydrogenation / reoxidation cycle. The extraction can preferably be carried out with substantially pure water, and a crude aqueous hydrogen peroxide solution is obtained. The crude aqueous hydrogen peroxide solution thus obtained can generally be further purified and / or concentrated by distillation. A crude aqueous hydrogen peroxide solution that has not been purified and / or concentrated by distillation can be used, or an aqueous hydrogen peroxide solution purified and / or concentrated by distillation can be used. In addition, the crude aqueous hydrogen peroxide solution can usually be subjected to a further extraction stage, wherein a suitable extractant, preferably an organic solvent, is used. More preferably, the organic solvent used for the further extraction stage is the same as the solvent used for the anthraquinone process. It is preferred that only one solvent in the working solution is used for extraction, and it is most preferred that only the most non-polar solvent in the working solution is used for extraction. In the case where the crude aqueous hydrogen peroxide solution is subjected to such a further extraction stage, a so-called crude washed hydrogen peroxide solution is obtained. According to a preferred embodiment of the present invention, a crude washed hydrogen peroxide solution is used as an aqueous hydrogen peroxide solution. For example, the preparation of a crude solution is described in European patent application EP 1 122 249 A1. Regarding the term "substantially pure water", reference is made to paragraph 10 on page 3 of EP 1 122 249 A1, which is incorporated herein by reference. Hydrogen peroxide can also be treated before use to remove trace metals, for example, as described in WO 2015 / 049327 A1.

[0083] It is contemplated that hydrogen peroxide is prepared in situ from hydrogen and oxygen in the epoxidation zone, preferably in the presence of a suitable noble metal catalyst contained in the epoxidation zone. Suitable noble metal catalysts preferably include one or more of palladium, platinum, silver, gold, rhodium, iridium, ruthenium and osmium. Preferably, the noble metal catalyst comprises palladium. The noble metal catalyst is preferably supported on a carrier, wherein the carrier preferably comprises SiO2, Al2O3, B2O3, GeO2, Ga2O3, ZrO2, TiO2, MgO, carbon and one or more zeolites, preferably one or more titanium zeolites. More preferably, the carrier comprises an epoxidation catalyst comprising a titanium zeolite. If hydrogen peroxide is prepared in situ from hydrogen and oxygen in the epoxidation zone, the reaction mixture comprises propylene, hydrogen, oxygen, water and an organic solvent.

[0084] Reaction conditions in epoxidation

[0085] For epoxidation, a reaction mixture comprising propylene, hydrogen, oxygen, water and an organic solvent is contacted in an epoxidation zone with an epoxidation catalyst, the epoxidation catalyst comprising the zeolite material having a framework structure comprising Si, O and Ti as described for the first aspect of the present invention or the molding according to the fourth aspect, the molding comprising the zeolite material having a framework structure comprising Si, O and Ti according to the first aspect as described above, and the reaction mixture is subjected to epoxidation reaction conditions in the epoxidation zone, and a mixture comprising propylene oxide, water and an organic solvent is obtained in the epoxidation zone.

[0086] In general, there are no specific restrictions on the conditions under which the epoxidation catalyst is contacted in the epoxidation zone, as long as effective epoxidation of propylene occurs. Preferably, the epoxidation reaction conditions include trickle bed conditions or fixed bed conditions, with fixed bed conditions being more preferred. Preferably, these conditions are applied to the reactor while the catalyst is present in the fixed bed. "Trickle bed conditions" preferably means that the reaction is preferably carried out at a temperature and pressure at which the reaction mixture is partially present in a liquid phase and partially in a gas phase, wherein the catalyst is present in a fixed bed. In an embodiment with fixed bed conditions, the reaction is preferably carried out at a temperature and pressure at which the reaction mixture is liquid and there is no gas phase in the epoxidation zone, wherein two or more liquid phases may be present, while the catalyst is present in a fixed bed. Preferably, the contact of the reaction mixture in the epoxidation zone with the epoxidation catalyst is carried out at an absolute pressure of 0.5 to 5.0 MPa, preferably 1.5 to 3.0 MPa, more preferably 1.8 to 2.8 MPa in the epoxidation zone.

[0087] In general, the contacting of the reaction mixture in the epoxidation zone with the epoxidation catalyst can be carried out in any suitable manner. Thus, for example, it can be carried out in a batch reactor or in at least one semi-continuously operated reactor or in at least one continuously operated reactor. The continuous operation mode is preferred.

[0088] Preferably, the contacting of the reaction mixture in the epoxidation zone with the epoxidation catalyst is carried out in at least one preferably continuously operated reactor, such as a tubular reactor or a tube bundle reactor, which preferably comprises at least one cooling jacket surrounding at least one tube. The cooling medium flows through the cooling jacket. The nature of the cooling medium is not particularly limited, as long as it is sufficient to adjust the temperature in the epoxidation zone. For example, the cooling medium comprises water, wherein it may additionally comprise additives, such as aliphatic C2 to C5 monohydric alcohols, aliphatic C2 to C5 diols and mixtures of two or more thereof. Preferably, ≥90 wt. %, more preferably ≥95 wt. % of the cooling medium is water, based on the total weight of the cooling medium. The temperature of the cooling medium is the temperature of the cooling medium used to adjust the temperature of the reaction mixture in the epoxidation zone, wherein the temperature is preferably adjusted by passing the cooling medium through a cooling jacket, wherein the temperature of the cooling medium is preferably the temperature of the cooling medium before adjusting the temperature of the reaction mixture, preferably the temperature of the cooling medium at the inlet of the cooling jacket.

[0089] Preferably, the contact of the reaction mixture in the epoxidation zone with the epoxidation catalyst takes place at a temperature in the epoxidation zone of 33 to 73° C., preferably 38 to 63° C., more preferably in a temperature range of 53 to 63° C. The temperature in the epoxidation zone is measured with ten thermocouples, i.e. ten thermocouples. The epoxidation zone is defined as the zone in which the reaction of hydrogen peroxide and propylene to produce propylene oxide still proceeds in detectable amounts (≥10 ppm propylene oxide). Preferably, the epoxidation zone is present over the entire length of the catalyst bed, i.e. preferably in the zone in the reactor in which the epoxidation catalyst is present (epoxidation zone=catalyst bed). The hot spot, i.e. the zone in which the maximum reaction takes place, is generally located in the front half of the catalyst bed, preferably ≥ six of the ten thermocouples are located in the front half of the catalyst bed. The temperature in the epoxidation zone is the average temperature determined by the temperature values ​​measured by all thermocouples located in the front half of the catalyst bed. Typically, the temperature values ​​measured by these thermocouples differ from each other in the range of 6 to 10° C. Preferably, the temperature of the cooling medium is the temperature of the cooling medium at the inlet into the reactor. Preferably, the temperature of the cooling medium is from 25 to 65°C, more preferably from 30 to 55°C, more preferably from 345 to 55°C. The temperature of the cooling medium in the range of 45 to 55°C is the optimum temperature range. Temperatures below 45°C are associated with the start-up phase of the epoxidation reaction and are too low for effective conditioning during the epoxidation reaction. Above 55°C, the decomposition of hydrogen peroxide and the formation of oxygen increase exponentially. In the range of 45 to 55°C of the cooling medium, the temperature of the epoxidation zone is in the optimum range of 53 to 63°C, thereby achieving maximum selectivity and optimum activity.

[0090] Epoxidation Zone

[0091] The reaction mixture is contacted with an epoxidation catalyst in an epoxidation zone, the epoxidation catalyst comprising the zeolite material having a framework structure comprising Si, O and Ti of the first aspect of the present invention or the molding of the fourth aspect, or comprising the molding of the zeolite material having a framework structure comprising Si, O and Ti of the first aspect above, respectively, and the reaction mixture is subjected to epoxidation reaction conditions in the epoxidation zone, and a mixture comprising propylene oxide, water and an organic solvent is obtained in the epoxidation zone.

[0092] In general, there are no specific restrictions on the design of the epoxidation zone, as long as it is suitable for carrying out the preferably continuous epoxidation reaction. Preferably, the epoxidation zone comprises one or more epoxidation subzones, wherein a given epoxidation subzone preferably consists of one or more epoxidation reactors, wherein there are no specific restrictions regarding the design of the one or more epoxidation reactors, as long as the reactors are suitable for carrying out the preferably continuous epoxidation reaction.

[0093] Preferably, the epoxidation zone comprises a first epoxidation sub-zone consisting of one or more epoxidation reactors A. The term "first epoxidation sub-zone" as used in the context of the present invention relates to an epoxidation sub-zone into which the reaction mixture is passed, wherein the epoxidation zone may comprise a further epoxidation sub-zone arranged downstream of the first epoxidation sub-zone. If the first epoxidation sub-zone consists of two or more epoxidation reactors A, preferably the two or more epoxidation reactors A are arranged in parallel. In this case, the reaction mixture is preferably passed into at least one epoxidation reactor A. For example, at least one of the reactors A may be shut down, for example for maintenance purposes and / or for regenerating the catalyst contained in at least one reactor A, while the reaction mixture is passed into the at least one epoxidation reactor A. If the first epoxidation sub-zone comprises two or more epoxidation reactors A, the reactors in operation are operated substantially identically, so that in each epoxidation reactor A in operation, the epoxidation conditions given in each reactor are within the same range. For example, the temperature in the epoxidation zone is within the same range in each reactor.

[0094] The temperature of the cooling medium is the temperature of the cooling medium used to adjust the temperature of the reaction mixture in the first epoxidation reaction subzone, wherein the temperature is preferably adjusted by passing the cooling medium through the cooling jacket of one or more epoxidation reactors A, wherein the temperature of the cooling medium is preferably the temperature of the cooling medium before adjusting the temperature of the reaction mixture, preferably the temperature of the cooling medium at the inlet of the cooling jacket of the one or more epoxidation reactors A. If the first epoxidation subzone includes two or more epoxidation reactors A, the temperature of the cooling medium is related to a given reactor A in operation of the first epoxidation subzone.

[0095] According to a first preferred embodiment, the epoxidation zone consists of a first epoxidation sub-zone.

[0096] According to a second preferred embodiment, the epoxidation zone additionally comprises a second epoxidation subzone consisting of one or more epoxidation reactors B, wherein, if the second epoxidation subzone comprises two or more epoxidation reactors B, the two or more epoxidation reactors B are arranged in parallel, wherein the second epoxidation subzone is arranged downstream of the first epoxidation subzone. In this case, the effluent stream obtained from the first epoxidation subzone, optionally after suitable intermediate treatment, is preferably passed to at least one epoxidation reactor B. For example, it is possible that, while the effluent stream obtained from the first epoxidation subzone, optionally after suitable intermediate treatment, is passed to at least one epoxidation reactor B, at least one reactor B is taken out of operation, for example for maintenance purposes and / or for regeneration of the catalyst contained in at least one reactor B. If the second epoxidation subzone comprises two or more epoxidation reactors B, the reactors in operation are operated substantially identically, so that in each epoxidation reactor B in operation, the given epoxidation conditions are within the same range in each reactor. Generally, it is conceivable that, in addition to the first epoxidation subzone and the second epoxidation subzone, the epoxidation subzone also comprises at least one further epoxidation subzone arranged downstream of the second epoxidation subzone. Preferably, according to the second preferred embodiment, the epoxidation zone consists of a first epoxidation sub-zone and a second epoxidation sub-zone.

[0097] Preferably, the temperature of the reaction mixture in the second epoxidation reaction subzone is not adjusted by passing a cooling medium through the cooling jacket of the one or more epoxidation reactors B. More preferably, the second epoxidation subzone is a substantially adiabatic epoxidation subzone. More preferably, the second epoxidation subzone is an adiabatic epoxidation subzone.

[0098] In a sixth aspect, the present invention relates to propylene oxide obtained or obtainable from the process according to the fifth aspect.

[0099] The present invention is further illustrated by the following set of embodiments and the combination of embodiments resulting from the indicated reference relationships and reverse references. In particular, it should be noted that in each case where the scope of the embodiments is mentioned, for example, in the context of terms such as "any one of embodiments 1 to 4...", each embodiment within the scope is meant to be explicitly disclosed by the skilled person, that is, the wording of the term should be understood by the skilled person as synonymous with "any one of embodiments 1, 2, 3 and 4...". In addition, it is explicitly pointed out that the following set of embodiments is not a set of claims that determine the scope of protection, but represents an appropriate structural part of the description of the general and preferred aspects of the present invention.

[0100] 1. A zeolitic material having a framework structure comprising Si, O and Ti, obtained or obtainable from a Ti-containing compound, wherein the APHA color of the Ti-containing compound is ≤300.

[0101] 2. A zeolite material obtained or obtainable from a Ti-containing compound according to embodiment 1 and having a framework structure comprising Si, O and Ti, wherein the Ti-containing compound comprises a Ti-containing alcoholate (alkoxide), preferably selected from Ti(O-alkyl)4, wherein each alkyl group is independently selected from a branched or unbranched C1 to C6 alkyl group; more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds; more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

[0102] 3. A zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to embodiment 1 or 2, wherein the Ti-containing compound comprises at least 90 wt.-%, preferably at least 95 wt.-%, more preferably at least 96 wt.-%, more preferably at least 97 wt.-%, more preferably at least 98 wt.-%, more preferably at least 99 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

[0103] 4. The zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of embodiments 1 to 3, wherein the Ti-containing compound comprises ≤ 10 wt.%, preferably ≤ 5 wt.%, more preferably ≤ 4 wt.%, more preferably ≤ 3 wt.%, more preferably ≤ 2 wt.%, more preferably ≤ 1 wt.% of a substance of formula (I), based on the total weight of the Ti-containing compound,

[0104]

[0105] Among them, R 1 and R 2 are independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups, R 3 is selected from a hydrogen atom, a branched or unbranched C1 to C6 alkyl group and a branched or unbranched C1 to C6 alkenyl group.

[0106] 5. A zeolite material obtained or obtainable from a Ti-containing compound according to embodiment 4 and having a framework structure comprising Si, O and Ti, wherein the substance of formula (I) is selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-dien-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone, 2,6-dimethyl-hept-2,5-dien-4-one) and a mixture of hept-2,5-dien-4-one and 2,6-dimethyl-hept-2,5-dien-4-one.

[0107] 6. A zeolite material obtained or obtainable from a Ti-containing compound according to any one of Embodiments 1 to 5 and having a framework structure comprising Si, O and Ti, wherein the titanium dioxide content of the zeolite material is ≤1.5 wt.%, preferably ≤1.2 wt.%, more preferably ≤1 wt.%, more preferably ≤0.5 wt.%, based on the total weight of the zeolite material, wherein, as determined according to Reference Example 7, preferably at least 98 wt.% of the titanium dioxide is in the form of anatase.

[0108] 7. A zeolite material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of Embodiments 1 to 6, wherein the zeolite material preferably has a crystallinity of greater than 85 wt %, preferably 85 to 95 wt %, more preferably 87 to 93 wt %, as determined according to Reference Example 7, based on the total weight of the zeolite material.

[0109] 8. A zeolite material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of Embodiments 1 to 7, wherein the zeolite material preferably exhibits a propylene oxide activity of at least 8.5 wt. %, more preferably 8.5 to 9.5 wt. %, more preferably 8.5 to 9.0 wt. %, as determined as described in Reference Example 1.

[0110] 9. The zeolite material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of embodiments 1 to 8, wherein the zeolite material exhibits a relative humidity of 440 to 580 m / s as determined in Reference Example 4. 2 / g, preferably 450 to 570m 2 / g BET specific surface area.

[0111] 10. The zeolitic material obtained or obtainable from a Ti-containing compound according to any one of embodiments 1 to 9 and having a framework structure comprising Si, O and Ti, wherein 95 to 100 wt.%, preferably 98 to 100 wt.%, more preferably 99 to 100 wt.%, more preferably 99.5 to 100 wt.%, more preferably 99.9 to 100 wt.% of the zeolitic material obtained or obtainable from the above-mentioned Ti-containing compound consists of Si, O, Ti and optionally H.

[0112] 11. The zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of embodiments 1 to 10, wherein the zeolitic material comprises Ti in an amount of 0.2 to 5 wt.-%, more preferably 0.5 to 4 wt.-%, more preferably 1.0 to 3 wt.-%, more preferably 1.2 to 2.5 wt.-%, more preferably 1.4 to 2.2 wt.-%, calculated as elemental Ti and based on the total weight of the zeolitic material.

[0113] 12. The zeolitic material having a framework structure comprising Si, O and Ti obtained or obtainable from a Ti-containing compound according to any one of embodiments 1 to 11, wherein the zeolitic material having a framework structure comprising Si, O and Ti is a zeolitic material having a Ti-containing compound, wherein the zeolitic material having a framework structure comprising Si, O and Ti is a zeolitic material having a Ti-containing compound, wherein the zeolitic material has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, wherein the Ti-containing compound has a Ti-containing compound, RA, GIS, GIU, GME, GON, GOO, HEU, IFR, ISV, ITE, ITH, ITQ, ITW, IWR, IWW, JBW, KFI, LAU, LEV, LIO, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MCM-22(S), MCM-36, MCM-56, MEI, MEL, MEP, MER, MIT-1, MMFI, MFS, MON, M OR, MSE, MSO, MTF, MTN, MTT, MTW, MWW, NAB, NAT, NEES, NON, NPO, OBW, OFF, OSI, OSO, PAR, PAU, PHI, PON , RHO, RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN SFO, SGT, SOD, SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, VFI, VNI, VSV, WEI, WEN, YUG, ZONSVR, SVY framework structure or a titanium zeolite of a mixed structure of two or more of these framework types; more preferably, the zeolite material having a framework structure including Si, O and Ti is a titanium zeolite having an MFI framework type, a MEL framework type, an MWW framework type, an MCM-22 (S) framework type, an MCM-56 framework type, an IEZ-MWW framework type, an MCM-36 framework type, an ITQ framework type, a BEA framework type, a MOR framework type or a mixed structure of two or more of these framework types; more preferably, an MFI framework type or an MWW framework type;More preferably, the zeolite material having a framework structure comprising Si, O and Ti has a framework type MFI; more preferably, the zeolite material having a framework structure comprising Si, O and Ti is titanium silicalite-1 (TS-1). ;

[0114] 13. A Ti-containing compound with an APHA color of ≤300, wherein the Ti-containing compound comprises a Ti-containing alcoholate, preferably selected from Ti(O-alkyl)4, wherein each alkyl group is independently selected from a branched or unbranched C1 to C6 alkyl, more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds, more preferably selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

[0115] 14. The Ti-containing compound having an APHA color ≤ 300 according to embodiment 13, wherein the Ti-containing compound comprises at least 90 wt %, preferably at least 95 wt %, more preferably at least 96 wt %, more preferably at least 97 wt %, more preferably at least 98 wt %, more preferably at least 99 wt % of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

[0116] 15. A Ti-containing compound having an APHA color of ≤300 according to embodiment 13 or 14, wherein the Ti-containing compound comprises ≤10 wt%, preferably ≤5 wt%, more preferably ≤4 wt%, more preferably ≤3 wt%, more preferably ≤2 wt%, more preferably ≤1 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound,

[0117]

[0118] Among them, R 1 and R 2 are independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups, R 3 is selected from a hydrogen atom, a branched or unbranched C1 to C6 alkyl group and a branched or unbranched C1 to C6 alkenyl group.

[0119] 16. A Ti-containing compound with an APHA color ≤300 according to any one of embodiments 13 to 15, wherein the substance of formula (I) is selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-dien-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone=2,6-dimethyl-hept-2,5-dien-4-one) and a mixture of hept-2,5-dien-4-one and 2,6-dimethyl-hept-2,5-dien-4-one.

[0120] 17. Use of the Ti-containing compound having an APHA color of ≤300 according to any one of embodiments 13 to 16 for preparing the zeolite material having a framework structure comprising Si, O and Ti according to any one of embodiments 1 to 12.

[0121] 18. A method for preparing a zeolite material having a framework structure comprising Si, O and Ti, wherein the zeolite material having a framework structure comprising Si, O and Ti is prepared from a Ti-containing compound having an APHA color ≤300, wherein the Ti-containing compound is as defined in any one of Embodiments 13 to 16.

[0122] 19. A molded article comprising: the zeolite material having a framework structure comprising Si, O and Ti according to any one of claims 1 to 12.

[0123] 20. The molded article according to embodiment 19, wherein the molded article exhibits a tortuosity parameter of <4, more preferably 1.0 to 2.5, more preferably 1.3 to 2.0, more preferably 1.40 to 1.80, more preferably 1.50 to 1.75, more preferably 1.55 to 1.70 relative to water, as determined as described in Reference Example 5.

[0124] 21. The molding according to embodiment 19 or 20, the pore volume of the molding determined according to DIN 66133:1993-06 preferably being from 0.1 to 1.5 ml / g.

[0125] 22. Use of the molded article according to any of embodiments 19 to 21 as an adsorbent, absorbent, catalyst or catalyst component, preferably as a catalyst or as a catalyst component, more preferably as a Lewis acid catalyst or as a Lewis acid catalyst component, as an isomerization catalyst or as an isomerization catalyst component, as an oxidation catalyst or as an oxidation catalyst component, as an aldol condensation catalyst or as an aldol condensation catalyst component, or as a Prins reaction catalyst or as a Prins reaction catalyst component.

[0126] 23. Use according to embodiments 19 to 20 as an oxidation catalyst or as an oxidation catalyst component, preferably as an epoxidation catalyst or as an epoxidation catalyst component, more preferably as an epoxidation catalyst.

[0127] 24. Use according to embodiment 23 for the epoxidation of organic compounds having at least one C-C double bond, preferably C2-C10 olefins, more preferably C2-C5 olefins, more preferably C2-C4 olefins, more preferably C2 or C3 olefins, more preferably propylene, more preferably for the epoxidation of propylene with hydrogen peroxide as oxidant, more preferably for the epoxidation of propylene with hydrogen peroxide as oxidant in a solvent comprising an alcohol, preferably methanol.

[0128] 25. A method for oxidizing an organic compound, comprising contacting the organic compound, preferably in continuous mode, with a catalyst comprising a molding according to any one of embodiments 19 to 21, the method preferably being used for epoxidizing an organic compound, more preferably for epoxidizing an organic compound having at least one C-C double bond, preferably a C2-C10 olefin, more preferably a C2-C5 olefin, more preferably a C2-C4 olefin, more preferably a C2 or C3 olefin, more preferably propylene.

[0129] 26. The method according to embodiment 25, wherein hydrogen peroxide is used as the oxidant, wherein the oxidation reaction is preferably carried out in a solvent, more preferably in a solvent comprising an alcohol (preferably methanol).

[0130] 27. A process for preparing propylene oxide, comprising reacting propylene with hydrogen peroxide in a solvent, preferably in a continuous manner, in the presence of a catalyst comprising a molded article according to any one of embodiments 19 to 21, to obtain propylene oxide.

[0131] 28. A process for preparing propylene oxide according to embodiment 27, wherein the reaction of propylene with hydrogen peroxide in a solvent in the presence of a catalyst is preferably carried out in an epoxidation zone, the absolute pressure in the epoxidation zone being 0.5 to 5.0 MPa, preferably 1.5 to 3.0 MPa, more preferably 1.8 to 2.8 MPa.

[0132] 29. A process for the preparation of propylene oxide according to embodiment 27 or 28, wherein the reaction of propylene with hydrogen peroxide in a solvent in the presence of a catalyst is carried out in the epoxidation zone at a temperature of 33 to 73°C, preferably 38 to 63°C, more preferably 53 to 63°C.

[0133] 30. According to any one of embodiments 27 to 29, a cooling medium is used to adjust the temperature of the epoxidation zone, wherein the temperature of the cooling medium is preferably in the range of 25 to 65°C, preferably 30 to 55°C, and more preferably in the range of 345 to 55°C.

[0134] 31. A process for preparing propylene oxide according to any one of embodiments 27 to 30, wherein during the process for preparing propylene oxide, the weight ratio of propylene:hydrogen peroxide (w / w) is 1:1 to 6:1, preferably 1:1 to 2:1 or 4:1 to 5:1.

[0135] 32. A process for preparing propylene oxide according to any one of embodiments 27 to 31, wherein the weight ratio of solvent:hydrogen peroxide (w / w) is preferably from 15:1 to 5:1, more preferably from 12:1 to 6:1, more preferably from 11:1 to 8:1.

[0136] 33. A method for preparing propylene oxide according to any one of embodiments 27 to 31, wherein the weight ratio of solvent:propylene in the reaction mixture (w / w) is 10:1 to 1:0.1, preferably 9:1 to 1:1, more preferably 9:1 to 7:1 or 1.5:1 to 1:1.

[0137] 34. The method for preparing propylene oxide of any one of embodiments 27 to 33, wherein the epoxidation reaction conditions comprise trickle bed conditions.

[0138] 35. The method for preparing propylene oxide according to any one of embodiments 27 to 33, wherein the epoxidation reaction conditions comprise fixed bed conditions.

[0139] 36. The method for preparing propylene oxide described in any one of embodiments 27 to 35, wherein the solvent is an organic solvent, preferably an organic epoxidation solvent, more preferably the organic solvent is selected from alcohol, acetonitrile, tert-butanol, propionitrile and a mixture of two or more thereof; more preferably selected from alcohol, acetonitrile and a mixture of alcohol and acetonitrile; more preferably the solvent includes at least alcohol; more preferably the organic solvent contains at least one alcohol.

[0140] 37. Propylene oxide obtained or obtainable by the process according to any one of embodiments 27 to 36.

[0141] It is expressly noted that the preceding set of embodiments is not a set of claims that determine the scope of protection, but rather represents a suitable structural part of the description of general and preferred aspects of the invention.

[0142] The present invention is further illustrated by the following reference examples, comparative examples and embodiments. Example

[0143] Reference Example 1: Determination of Propylene Oxide Activity and Pressure Drop Rate (PO Test)

[0144] In the PO test (a preliminary test procedure for evaluating the possible suitability of the powders as catalysts for the epoxidation of propylene, described in detail below), the powders are tested in a glass autoclave by reacting propylene with an aqueous hydrogen peroxide solution (30% by weight) to produce propylene oxide. Specifically, 0.5 g of the corresponding powder is introduced into a glass autoclave together with 45 ml of methanol or 45 ml of acetonitrile, which is cooled to -25°C. 20 ml of liquid propylene are pressed into the glass autoclave, and the glass autoclave is heated to 0°C. At this temperature, 18 g of an aqueous hydrogen peroxide solution (30% by weight in water) are introduced into the glass autoclave. After a reaction time of 5 hours at 0°C, the mixture is heated to room temperature (25°C) and the liquid phase is analyzed by gas chromatography for its propylene oxide content. The propylene oxide content of the liquid phase (in % by weight) is the result of the PO test, i.e. the propylene oxide activity of the powder.

[0145] Reference Example 2: Determination of Catalytic Performance of Propylene Epoxidation

[0146] In a continuous epoxidation reaction apparatus, 15 g of a molding of the corresponding TS-1 catalyst in the form of strands as described in the following examples and comparative examples were added to a vertically arranged tubular reactor (length: 1.4 m, outer diameter: 10 mm, inner diameter: 4 mm; material: 1.4571 type stainless austenitic steel) equipped with a cooling jacket for thermostating. The area in the reactor covered by the molding is referred to as the catalyst bed. The remaining reactor volume was filled with inert material (talc balls, diameter 2 mm) at the lower end of the reactor to a height of about 5 cm, and the remainder at the top of the reactor. The temperature in the epoxidation zone (=catalyst bed) was measured with a ten-fold thermocouple (ten thermocouples, each made of 1.4571 type austenitic stainless steel). Six of the ten thermocouples were located in the front half of the catalyst bed.

[0147] Feed streams were provided for all raw materials methanol, propylene and hydrogen peroxide. Through the reactor, the raw materials were passed at the following flow rates: methanol (49 g / h); hydrogen peroxide (9 g / h; used as an aqueous hydrogen peroxide solution with a hydrogen peroxide content of 40% by weight); propylene (7 g / h; polymer grade).

[0148] The average temperature in the epoxidation zone was adjusted in the range of 60 to 70° C. by means of a cooling medium passing through the cooling jacket, so that the hydrogen peroxide conversion, determined on the basis of the reaction mixture leaving the reactor, was substantially constant at 90%. The pressure in the reactor was kept constant at 21 bar (abs), and the reaction mixture—except for the fixed bed catalyst—consisted of a single liquid phase.

[0149] The reactor effluent stream downstream of the pressure control valve was collected, weighed and analyzed. The organic components were analyzed in two separate gas chromatographs. The hydrogen peroxide content was determined colorimetrically using the titanyl sulfate method. The selectivity for propylene oxide was determined relative to hydrogen peroxide (S(H2O2) vs. PO) and was calculated as 100 times the number of moles of propylene oxide in the effluent stream (mol(PO produced)) divided by the number of moles of peroxide in the feed (mol(H2O2 fed)) as follows (1):

[0150]

[0151] Reference Example 3: Determination of N2 adsorption / desorption isotherms

[0152] Nitrogen adsorption / desorption isotherms (N2 adsorption isotherms) were determined at 77 K according to the method disclosed in DIN 66131: 1993-07. The N2 adsorption isotherms at liquid nitrogen temperature were measured using a Micrometrics ASAP 2020M and a Tristar system.

[0153] Reference Example 4: Determination of BET specific surface area

[0154] The BET specific surface area was determined by nitrogen physical adsorption at 77 K according to the method disclosed in DIN 66131:1993-07. The N2 adsorption isotherm at liquid nitrogen temperature was measured using a Micrometrics ASAP 2020M and a Tristar system to determine the BET specific surface area as described in Reference Example 3.

[0155] Reference Example 5: Determination of tortuosity parameters relative to water

[0156] PFG NMR enables non-destructive examination of the thermal molecular motions of adsorbed molecules in free gases and liquids, in macroscopic and supramolecular solutions, and in porous systems. The principles and applications are described in US 2007 / 0099299 A1. The tortuosity is calculated from the diffusion coefficient obtained by NMR as follows. The tortuosity of a porous material is calculated from the self-diffusion coefficient (D eff) and the self-diffusion coefficient (D0) of the free liquid of formula (2) (see S. Kolitcheff, E. Jolimaitre, A. Hugon, J. Verstraete, M. Rivallan, PL. Carrette, F. Couenne and M. Tayakout-Fayolle, Catal. Sci. Technol., 2018, 8, 4537; and F. Elwinger, P. Pourmand, and I. Furo, J. Phys. Chem. C. 2017, 121, 13757-13764):

[0157]

[0158] The free diffusion coefficient of water at 20°C is 2.02x10 -9 m 2 s -1 (See M. Holz, SR Heil and A. Sacco. Phys. Chem. Chem. Phys., 2000, 2, 4740-4742).

[0159] Determination of diffusion coefficients by NMR

[0160] The samples for NMR analysis were prepared by drying a small amount (0.05-0.2 g) of the molded catalyst overnight in a NMR measuring tube under vacuum at T>350°C. The samples were then filled to 90% of the catalyst support pore volume (determined by Hg porosimetry) with nanopure water (Millipore Advantage A10) via a vacuum line. The filled samples were then flame sealed into the measuring tube and left overnight before measurement.

[0161] The D of water in the catalyst materials was carried out using a Bruker Avance III NMR spectrometer at 400 MHz 1H resonance frequency at 20 °C and 1 bar. eff NMR analysis. A Bruker Diff50 probe was used with a Bruker Great 60A gradient amplifier. The temperature was maintained at 20°C using a water-cooled gradient coil. Figure 1b, The pulse program used for PFGNMR self-diffusion analysis is stimulated spin echo with pulsed field gradient. For each sample, the spin echo decay curve is measured at different diffusion times (between 20 and 100 ms) by gradually increasing the intensity of the field gradient (to a maximum value of gmax = 3T / m). The gradient pulse length is 1 ms. The spin echo decay curve is fitted to equation 6 of US 2007 / 0099299 A. The slope of each line corresponds to the diffusion coefficient. According to formula (2) above, the tortuosity of each catalyst support is calculated using the average diffusion coefficient across all diffusion times.

[0162] Reference Example 6: Preparation of molded articles using colloidal silica binder precursor

[0163] Forming: Particles of the corresponding zeolite materials (105.3 g) from Examples 3 and 4 and Comparative Examples 1 and 2 below and carboxymethyl cellulose (4.0 g; Walocel (TM), Mw=15,000 g) were mixed in a kneader for 5 minutes. Then, an aqueous polystyrene dispersion (100.7 g; 33.7 g polystyrene) was added continuously. After 10 minutes, polyethylene oxide (1.33 g) was added. After 10 minutes, 70 g of AS 40 (a 40 wt. % silica solution in water). After a further 10 minutes, 10 ml of water were added and after a further 5 minutes, another 10 ml of water were added. The total kneading time was 40 minutes. The resulting moldable mass obtained from the kneading was extruded through a matrix with circular holes of 1.9 mm in diameter at a pressure of 130 bar. The obtained wire was dried in an oven at a temperature of 120° C. in air for 4 hours and calcined in air at a temperature of 490° C. for 5 hours.

[0164] Water treatment: 36g of these wires were divided into four portions (9g each), each of which was mixed with 180g of deionized water. The resulting mixture was heated to 145°C in an autoclave and kept for 8 hours. Thereafter, the water-treated wires obtained were separated and sieved with a 0.8mm sieve. The obtained wires were then washed with deionized water and subjected to a nitrogen flow at ambient temperature. The washed wires were then dried in air at a temperature of 120°C for 4 hours and then calcined in air at a temperature of 450°C for 2 hours.

[0165] Reference Example 7: X-ray powder diffraction and crystallinity determination

[0166] Powder X-ray diffraction (PXRD) data were collected using a diffractometer (D8 Advance Series II, Bruker AXS GmbH) equipped with a LYNXEYE detector operating at 40 kV and 40 mA using a copper anode X-ray tube. The geometry was Bragg–Brentano and an air scattering shield was used to reduce air scattering.

[0167] Calculation of crystallinity: The crystallinity of the samples was determined using the software DIFFRAC.EVA provided by Bruker AXS GmbH, Karlsruhe. The method is described on page 121 of the user manual. The default parameters for the calculation were used.

[0168] Calculation of phase composition: The phase composition was calculated for the raw data using the modeling software DIFFRAC.TOPAS provided by Bruker AXS GmbH, Karlsruhe. The crystal structure of the identified phases, the instrument parameters and the crystallite size of the individual phases were used to simulate the diffraction pattern. This was fitted to the data in addition to a function modeling the background intensity.

[0169] Data collection: The samples were homogenized in a mortar and then pressed into a standard flat sample holder supplied by Bruker AXS GmbH for Bragg-Brentano geometry data collection. A glass plate was used to compress and flatten the sample powder to achieve a flat surface. Data were collected over an angular range of 2 to 70° 2θ with a step size of 0.02° 2θ, while the variable divergence slit was set to an angle of 0.1°. The crystalline content describes the intensity of the crystalline signal relative to the total scattered intensity (DIFFRAC.EVA User Manual, Bruker AXS GmbH, Karlsruhe).

[0170] Example 1: Determination of APHA Chroma and Organic Impurities

[0171] A) Determination of organic matter in tetraethyl orthotitanate (Ti(OEt)4) with different APHA chromaticities and tetraisopropyl orthotitanate (Ti(OPr)4) with different APHA chromaticities

[0172] The organic content of Ti(OEt)4) samples with different APHA chromaticity was analyzed. APHA chromaticity is used according to DIN ENISO 6271:2016-05 (Hazen color value). 620 colorimeter.

[0173] Before quantifying the organic impurities, the precipitate (TiO2) formed over time was filtered off. Quantification was performed by HPLC / CE - derivatized with DNPH (2,4-dinitrophenylhydrazine); column Symmetry Shield RP18, 5μm 2.1×150mm, Waters; 45°C; 0.4 ml / min; run time 45 minutes, UV detector. The material in the organic phase was double checked by GC / MS (column: Restek #13623; RXI-5silMS, 30m×0.25mm×0.25μm; inlet temperature: 200°C; temperature program: 1) 35°C 7min, 2) heating to 220°C at 8°C / min), and the results are shown in Table 1 below:

[0174] Table 1

[0175] The amount of hepta-2,5-dien-4-one in Ti(OEt)4 samples at different APHA chromaticities

[0176] APHA Chroma Amount of hepta-2,5-dien-4-one [ppm] 68 0 157 1068 256 2440 278 2829 316 3277

[0177] Acetaldehyde and crotonaldehyde were clearly identified by comparison with the database spectrum; quantification in samples with APHA color 68 was performed by HPLC / CE - derivatized with DNPH (2,4-dinitrophenylhydrazine); chromatographic column: Symmetry ShieldRP18, 5μm 2.1*150mm, Waters; 45°C; 0.4 ml / min; running time 45 minutes, UV detector. The corresponding amount is:

[0178] Acetaldehyde: 55 mg / kg (55 ppm by weight)

[0179] Crotonaldehyde: 12 mg / kg (12 ppm by weight)

[0180] Organic content analysis of tetraisopropyl orthotitanate (Ti(OPr)4) samples with different APHA chromaticity. APHA chromaticity is used according to DIN EN ISO 6271:2016-05 (Hazen color value). 620 colorimeter.

[0181] Before quantifying the organic impurities, the precipitate (TiO2) formed over time was filtered off. The organic phase was then analyzed by GC / MS (chromatographic column: Restek #13623; RXI-5silMS, 30m×0,25mm×0,25μm; injection port temperature: 200°C; temperature program: 1) 35°C for 7min, 2) heating to 220°C at 8°C / min), and the results are shown in Table 2 below:

[0182] Table 2

[0183] The amount of 2,6-dimethyl-hept-2,5-dien-4-one in Ti(OPr)4 samples with different APHA chromaticity

[0184] APHA Chroma Amount of 2,6-dimethyl-hept-2,5-dien-4-one [ppm] 75 0 212 1980 323 3100

[0185] Acetone and 4-methyl-3-penten-2-one were clearly identified by comparison with the database spectrum; quantification in samples with APHA color 75 was performed by HPLC / CE - derivatization with DNPH (2,4-dinitrophenylhydrazine); column: Symmetry Shield RP18, 5μm 2.1×150mm, Waters; 45°C; 0.4 ml / min; run time 45 min, UV detector. The corresponding amount is:

[0186] Acetone: 23 mg / kg (23 ppm)

[0187] 4-Methyl-3-pentan-2-one: 5 mg / kg (5 ppm)

[0188] B) Determination of APHA color of tetraethyl orthotitanate (Ti(OEt)4) in different samples

[0189] According to DIN EN ISO 6271:2016-05 (Hazen colorimetric), use The APHA chromaticity of different tetraethyl orthotitanate (Ti(OEt)4) samples was measured using a 620 colorimeter.

[0190] A fresh and visually clear tetraethyl orthotitanate sample (tetraethyl orthotitanate purchased from Merck) was used as a reference. The results are shown in Table 3.

[0191] Table 3

[0192] APHA chromaticity of different tetraethyl orthotitanate samples

[0193] Sample APHA Chroma Reference 102 1 251 2 300 3 >1000 4 >1000

[0194] C) Determination of APHA Chroma of Tetrabutyl Ortho Titanate in Different (Ti(OBu)4) Samples

[0195] According to DIN EN ISO 6271:2016-05 (Hazen colorimetric), use The APHA chromaticity of different tetrabutyl orthotitanate (Ti(OBu)4) samples was measured using a 620 colorimeter.

[0196] A fresh and visually clear tetrabutyl orthotitanate sample (tetrabutyl orthotitanate purchased from Merck) was used as a reference. The results are shown in Table 4.

[0197] Table 4

[0198] APHA chromaticity of different tetrabutyl orthotitanate samples

[0199] Sample APHA Chroma 5 171 6 537

[0200] Example 2: Synthesis of TS1-1 Catalyst

[0201] Titanium silicate zeolite-1 (TS-1) powder was prepared according to the following formula:

[0202] Initial Weight:

[0203] Tetraethyl orthosilicate 500g

[0204] Tetraethyl orthotitanate (reference from Example 1) 15 g

[0205] Tetrapropylammonium hydroxide (40 wt% aqueous solution) 220 g

[0206] Deionized water 300g

[0207] Tetraethyl orthosilicate and tetraethyl orthotitanate with an APHA color of 102 (reference example 1) were added to a four-necked flask. Deionized water and an aqueous solution of tetrapropylammonium hydroxide were added under stirring at 200 U / min. The pH value of the solution measured by a pH electrode was 13.54. The solution was hydrolyzed at room temperature (25°C) for 60 minutes, with the temperature rising to 60°C.

[0208] The ethanol formed during the reaction was removed by distillation until the temperature in the bottom pool of the flask reached 95°C. The amount of ethanol removed was 547 g, and the pH value in the bottom pool was 11.98. The remaining gel was stirred until its temperature was 40°C. 530 g of deionized water were added under stirring, and the pH value of the resulting solution was measured with a pH electrode to be 11.52.

[0209] The resulting solution was then transferred to an autoclave and heated to 175° C. with stirring. Crystallization was carried out at 175° C. under autogenous pressure for 16 hours with stirring (rotation speed 200 U / min, torque range 50 to 70 N / cm, pressure range 9 to 10 bar).

[0210] The suspension containing titanium silicalite-1 crystals was transferred to another container, where it was diluted with deionized water in a volume ratio of 1:1 under stirring at 200 U / min (Teflon-horseshoe mixer). Afterwards, about 215.8 g of a 10 wt % HNO3 aqueous solution was added, so that the pH value measured with a pH electrode dropped to 7, followed by filtration (porcelain suction, blue ribbon filter). The filter cake was washed 3 times, each time with 1000 ml of deionized water, then dried at 120°C for 4 hours in a ventilated muffle furnace, and then calcined at 490°C for 5 hours in air (heating rate 2°C / min).

[0211] Based on the weight of the initial tetraethyl orthotitanate, 88 wt% of the zeolitic material in powder form was obtained. Based on the crystallinity and phase composition data determined according to Reference Example 7, 100 wt% of the particles obtained had a TS-1 structure (anatase content (TiO2) of 0 wt%), showing a Ti content of 2.0 wt% (calculated as elemental Ti) and a Si content of 42 wt% (calculated as elemental Si), based on the total weight of the particles obtained. The BET specific surface area of ​​the powder determined according to Reference Example 4 was 563 m 2 / g.

[0212] The powder absorption of diffuse reflected light was measured using a UV / VIS / NIR spectrophotometer Lambda 950 with a 150 mm integrating sphere (Ulbrichtkugel) with an indicator light switching point. Based on the %R spectrum, a Kubelka-Munk transformation (KM) was performed and the results are shown in Figure 2 No obvious bands were found above 330 nm (about 330 nm to about 350 nm), indicating that there was no significant amount of anatase.

[0213] According to Reference Example 6, a molded article was prepared.

[0214] Example 3: Synthesis of TS1-1 Catalyst

[0215] Titanium silicate zeolite-1 (TS-1) powder was prepared according to the following formula:

[0216] Initial Weight:

[0217] Tetraethyl orthosilicate 500g

[0218] Tetraethyl orthotitanate (sample No. 1 from Example 1) 15 g

[0219] Tetrapropylammonium hydroxide (40 wt% aqueous solution) 220 g

[0220] Deionized water 300g

[0221] Tetraethyl orthosilicate and tetraethyl orthotitanate with an APHA color of 251 (sample No. 1 from Example 1) were added to a four-necked flask. Deionized water and tetrapropylammonium hydroxide aqueous solution were added under stirring at 200 U / min. The pH value of the solution was measured with a pH electrode and was 13.56. Further steps were carried out according to Example 2.

[0222] After calcination, 93% by weight of the zeolitic material in powder form was obtained, based on the weight of the initial tetraethyl orthotitanate. Based on the crystallinity and phase composition data determined according to Reference Example 7, 100% of the resulting particles had a TS-1 structure (anatase (TiO2) content of 0% by weight). Based on the total weight of the resulting particles, the particles exhibited a Ti content of 2.0% by weight (calculated as elemental Ti) and a Si content of 44% by weight (calculated as elemental Si). The BET specific surface area of ​​the powder determined according to Reference Example 4 was 462 m 2 / g.

[0223] The absorption of diffuse reflected light by the powder was measured according to Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) was as follows: Figure 2 No obvious bands were found above 330 nm (about 330 nm to about 350 nm), indicating that there was no significant amount of anatase.

[0224] The moldings were prepared according to Reference Example 6. The tortuosity parameter of the wire obtained after water treatment and calcination was 1.6 relative to water, determined according to Reference Example 5. The porosity / pore volume determined by Hg porosimetry according to DIN 66133:1993-06 was 0.92 ml / g.

[0225] Example 4: Preparation of TS1-1 catalyst

[0226] Titanium silicate zeolite-1 (TS-1) powder was prepared according to the following formula:

[0227] Initial Weight:

[0228] Tetraethyl orthosilicate 500g

[0229] Tetraethyl orthotitanate (sample No. 2 from Example 1) 15 g

[0230] Tetrapropylammonium hydroxide (40 wt% aqueous solution) 220 g

[0231] Deionized water 300g

[0232] Tetraethyl orthosilicate and tetraethyl orthotitanate with an APHA color of 300 (sample No. 2 from Example 1) were added to a four-necked flask. Deionized water and tetrapropylammonium hydroxide aqueous solution were added under stirring at 200 U / min. The pH value of the solution was measured with a pH electrode and was 13.56. Further steps were carried out according to Example 2.

[0233] After calcination, 91% by weight of the zeolitic material in powder form, based on the initial weight of tetraethyl orthotitanate, was obtained. Based on the crystallinity and phase composition data determined according to Reference Example 7, 99.0% by weight of the resulting particles had a TS-1 structure, while 1.0% by weight were anatase, based on the total weight of the particles obtained. The particles exhibited a Ti content of 2.0% by weight (calculated as elemental Ti) and a Si content of 45% by weight, based on the total weight of the particles obtained. The BET specific surface area of ​​the powder, determined according to Reference Example 4, was 437 m 2 / g.

[0234] The absorption of diffuse reflected light by the powder was measured according to Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) was as follows: Figure 2 A significant band can be found above 330 nm (about 330 nm to about 350 nm), which indicates the presence of a large amount of anatase.

[0235] The moldings were prepared according to Reference Example 6. The tortuosity parameter of the wire obtained after water treatment and calcination was 2.2 with respect to water, as determined according to Reference Example 5. The porosity / pore volume determined by Hg porosimetry according to DIN 66133:1993-06 was 0.84 ml / g.

[0236] Comparative Example 1: Synthesis of TS1-1 Catalyst

[0237] Titanium silicate zeolite-1 (TS-1) powder was prepared according to the following formula:

[0238] Initial Weight:

[0239] Tetraethyl orthosilicate 500g

[0240] Tetraethyl orthotitanate (sample No. 3 from Example 1) 15 g

[0241] Tetrapropylammonium hydroxide (40 wt% aqueous solution) 220 g

[0242] Deionized water 300g

[0243] Tetraethyl orthosilicate and tetraethyl orthotitanate with an APHA color number of >1000 (sample No. 3 from Example 1) were added to a four-necked flask. Deionized water and an aqueous solution of tetrapropylammonium hydroxide were added under stirring at 200 U / min. The pH value of the solution was determined to be 13.48 using a pH electrode. Further steps were carried out according to Example 2.

[0244] After calcination, 92% by weight of the zeolitic material in powder form was obtained, based on the weight of the initial tetraethyl orthotitanate. According to the data of crystallinity and phase composition determined according to Reference Example 7, 98.7% by weight of the particles obtained were of TS-1 structure, and 1.3% by weight were of anatase, based on the total weight of the particles obtained. The particles showed a Ti content of 2.0% by weight (calculated as elemental Ti), and a Si content of 43% by weight, based on the total weight of the particles obtained. The BET specific surface area of ​​the powder measured according to Reference Example 4 was 455 m 2 / g.

[0245] The absorption of diffuse reflected light by the powder was measured according to Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) was as follows: Figure 2 A significant band can be found above 330 nm (about 330 nm to about 350 nm), which indicates the presence of a large amount of anatase.

[0246] The moldings were prepared according to Reference Example 6. The tortuosity parameter of the wire obtained after water treatment and calcination was 1.4 relative to water, determined according to Reference Example 5. The porosity / pore volume determined by Hg porosimetry according to DIN 66133:1993-06 was 0.91 ml / g.

[0247] Comparative Example 2: Synthesis of TS1-1 Catalyst

[0248] Titanium silicate zeolite-1 (TS-1) powder was prepared according to the following formula:

[0249] Initial Weight:

[0250] Tetraethyl orthosilicate 500g

[0251] Tetraethyl orthotitanate (sample No. 4 from Example 1) 15 g

[0252] Tetrapropylammonium hydroxide (40 wt% aqueous solution) 220 g

[0253] Deionized water 300g

[0254] Tetraethyl orthosilicate and tetraethyl orthotitanate with APHA color > 1000 (sample No. 4 from Example 1) were added to a four-necked flask. Deionized water and tetrapropylammonium hydroxide aqueous solution were added under stirring at 200 U / min. The pH value of the solution was measured with a pH electrode and was 13.48. Further steps were carried out according to Example 2.

[0255] After calcination, 89% by weight of the zeolitic material in powder form was obtained, based on the weight of the initial tetraethyl orthotitanate. According to the crystallinity and phase composition data determined according to Reference Example 7, 98.5% by weight of the resulting particles had a TS-1 structure, while 1.5% by weight were anatase, based on the total weight of the resulting particles. The particles exhibited a Ti content of 2.0% by weight (calculated as elemental Ti) and a Si content of 44% by weight, based on the total weight of the resulting particles. The BET specific surface area of ​​the powder determined according to Reference Example 4 was 461 m 2 / g.

[0256] The XRD spectrum of the obtained solid is shown in Figure 1 .

[0257] The absorption of diffuse reflected light by the powder was measured according to Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) was as follows: Figure 2 A significant band can be found above 330 nm (about 330 nm to about 350 nm), which indicates the presence of a large amount of anatase.

[0258] The moldings were prepared according to Reference Example 6. The tortuosity parameter of the wire obtained after water treatment and calcination was 1.3 relative to water, as determined according to Reference Example 5. The porosity / pore volume determined by Hg porosimetry according to DIN 66133:1993-06 was 0.98 ml / g.

[0259] Example 6: Synthesis of TiMWW catalyst

[0260] A deboronated zeolitic material having an MWW framework type was prepared according to Example 1 of WO 2013 / 117537 A1. The resulting spray-dried deboronated zeolitic material of framework type MWW (deboronated MWW) had a B content of 0.08 wt.-%, a Si content of 42 wt.-% and a TOC of 0.23 wt.-%.

[0261] Titanium zeolite of MWW framework type (TiMWW) was prepared in powder form according to the following recipe:

[0262] Initial Weight:

[0263] Piperidine 303.1 g

[0264] Tetrabutyl orthosilicate 43.13g

[0265] Deboronized MWW 200g

[0266] Deionized water 821.8g

[0267] Piperidine was added to a beaker containing 500 g of deionized water and stirred at 200 rpm for 10 minutes. Tetrabutyl orthotitanate (Sample No. 5 from Example 1) with APHA color of 171 was added under stirring. After stirring for 15 minutes, 321.8 g of demineralized water was added and stirred for another 15 minutes. Deboronated MWW was added and the suspension was stirred for 60 minutes. The suspension was then transferred to a 2.5 liter autoclave and heated to 170°C and maintained for 48 hours under stirring. After cooling, the suspension was filtered with a porcelain filter, washed with deionized water, and the filter cake was dried at 120°C for 10 hours. 90 g of the dried material was added to a 4-necked round-bottom flask containing 1800 g of 10% HNO3 solution under stirring (200 rpm). The suspension was heated to 100°C under reflux and maintained for 1 hour, filtered with a porcelain filter after cooling and washed 3 times with 1000 ml of deionized water. The filter cake was dried at 120°C for 4 hours and the powder was calcined at 550°C for 5 hours (heating ramp 2°C / min).

[0268] After calcination, a zeolitic material (TiMWW) was obtained in powder form. The degree of crystallinity determined according to Example Reference 7 was 82%. The particles exhibited a Ti content (calculated as elemental Ti) of 2.1% by weight and a Si content of 41% by weight, based on the total weight of the particles obtained.

[0269] The absorption of diffuse reflected light by the powder is as described in Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) is as follows: Figure 3 No obvious bands were found above 330 nm (about 330 nm to about 350 nm) that would indicate the presence of a large amount of anatase.

[0270] Comparative Example 3: Synthesis of TiMWW Catalyst

[0271] A deboronated zeolitic material having an MWW framework type was prepared according to Example 1 of WO 2013 / 117537 A1. The obtained spray-dried deboronated zeolitic material of framework type MWW (deboronated MWW) exhibited a B content of 0.08 wt.-%, a Si content of 42 wt.-%, and a TOC of 0.23 wt.-%.

[0272] Titanium zeolite of MWW framework type (TiMWW) was prepared in powder form according to the following recipe:

[0273] Initial Weight:

[0274] Piperidine 303.1 g

[0275] Tetrabutyl orthotitanate 43.13g

[0276] Deboronized MWW 200g

[0277] Deionized water 821.8g

[0278] Piperidine was added to a beaker containing 500 g of deionized sodium and stirred at 200 rpm for 10 minutes. Tetrabutyl orthotitanate (sample No. 6 from Example 1) with an APHA color of 537 was added under stirring. After stirring for 15 minutes, 321.8 g of demineralized water was added and stirred for another 15 minutes. Deboronated MWW was added and the suspension was stirred for 60 minutes. The suspension was then transferred to a 2.5-liter autoclave and heated to 170° C. and maintained for 48 hours under stirring. After cooling, the suspension was filtered with a porcelain filter, washed with deionized water, and the filter cake was dried at 120° C. for 10 hours. 90 g of the dried material was added to a 4-necked round-bottom flask containing 1800 g of 10% HNO3 solution under stirring (200 rpm). The suspension was heated to 100° C. under reflux and maintained for 1 hour, filtered with a porcelain filter after cooling and washed 3 times with 1000 ml of deionized water. The filter cake was dried at 120°C for 4 hours and the powder was calcined at 550°C for 5 hours (heating ramp 2°C / min).

[0279] After calcination, a zeolitic material (TiMWW) was obtained in powder form. The degree of crystallinity determined according to Example Reference 7 was 74%. The particles exhibited a Ti content (calculated as elemental Ti) of 1.9% by weight, and a Si content of 42% by weight, based on the total weight of the particles obtained.

[0280] The absorption of diffusely reflected light by the powder was determined as described in Example 2, and the spectrum obtained by Kubelka-Munk transformation (KM) was as follows: Figure 3 As shown. Figure 3 The enlarged portion on the right shows a shoulder above 330 nm (about 330 nm to about 350 nm), indicating the presence of a certain amount of anatase.

[0281] Example 7: Epoxidation of Propylene

[0282] Example 7.1: Preliminary Tests - PO Tests

[0283] a) TS-1 and methanol as solvent

[0284] The TS-1 powders from Examples 2, 3 and 4 and Comparative Examples 1 and 2 were preliminarily tested for their general suitability as epoxidation catalysts using methanol (45 ml) according to the PO test described in Reference Example 1. The individual resulting values ​​for propylene oxide activity and a summary of the powder properties are shown in Table 5 below.

[0285] Table 5 Catalytic test results and TS-1 powder properties according to Reference Example 1

[0286]

[0287] The above results show that the catalyst prepared from tetraethyl orthotitanate with an APHA color number greater than 300 has poor epoxidation performance. Obviously, according to the PO test, TS-1 powder prepared from tetraethyl orthotitanate with an APHA color of ≤300 shows very good propylene oxide activity and is a promising alternative catalyst for industrial continuous epoxidation reactions.

[0288] b) TiMWW and acetonitrile as solvent

[0289] The general suitability of the TiMWW powders from Example 6 and Comparative Example 3 as epoxidation catalysts was preliminarily tested using acetonitrile (45 ml) as solvent according to the PO test described in Reference Example 1. The individual resulting values ​​for propylene oxide activity as well as a summary of the powder properties are shown in Table 6 below.

[0290] Table 6 Catalytic test results and TiMWW powder properties according to Reference Example 1

[0291]

[0292] The above results show that TiMWW catalysts prepared from tetrabutyl orthotitanate with an APHA color > 300 already exhibit good propylene oxide activity according to the PO test. However, it can be seen that the use of titanium-containing compounds with an APHA color < 300 further improves the results of the PO test, indicating that TiMWW powders prepared from tetrabutyl orthotitanate with an APHA color ≤ 300 are promising alternatives for industrial continuous epoxidation catalysts.

[0293] Example 7.2: Catalytic properties of molded articles in a continuous epoxidation reaction

[0294] The properties of the molded articles of Examples 2, 3, 4 and Comparative Examples 1 and 2 (TS-1 catalyst) were investigated in a continuous epoxidation reaction as described in Reference Example 2. Based on the reaction mixture leaving the reactor, the hydrogen peroxide conversion was kept substantially constant at 90%, as described in Reference Example 2. The selectivity of a given propylene oxide relative to hydrogen peroxide (S(H2O2) to PO) was determined as a function of the time on stream (TOS). The epoxidation was carried out for 550 hours.

[0295] The final selectivity to propylene oxide (PO) (S(H2O2) to PO) based on the data measured at the end of the epoxidation (at 500 hours), calculated according to Reference Example 1, the temperature of the cooling medium and the average temperature of the epoxidation zone are shown in Table 7. Table 7 below also shows the APHA color of the corresponding Ti-containing compounds used to prepare the corresponding TS-1 powders and subsequently the corresponding moldings.

[0296] Table 7 Properties of Molded Articles Used in Continuous Epoxidation

[0297]

[0298] The results of the continuous epoxidation reaction are shown in Figures 4 to 6 wherein the selectivity of propylene oxide relative to hydrogen peroxide (H2O2) (S(H2O2) to PO) is determined according to Reference Example 2 (see Figure 5 and 6 ). The experiments show that the performance of the TS-1 catalyst decreases with increasing APHA color of the Ti-containing compound used for the synthesis of the catalyst powders according to Examples 2-4 and Comparative Examples 1-2. Even if the results of the different TS-1 catalysts appear comparable during the initial operating time, it can be seen that a significant difference is revealed at longer operating times (e.g. >150 h, preferably >200 h, more preferably >250 h): at APHA values ​​above 300, higher temperatures in the epoxidation zone (and therefore higher cooling medium temperatures) are required to maintain the hydrogen peroxide conversion at values ​​≥90% (see Figure 4 and 6 ). However, at these high APHA numbers of the titanium-containing compounds, the selectivity is <84% at 500 hours. The TS-1 catalyst based on a Ti-containing compound with an APHA color of 300 at least leads to a selectivity of about 85% at 500 hours. The TS-1 catalyst based on a Ti-containing compound with an APHA color of <300 produces significantly better results at 500 hours, since the selectivity is significantly higher than 92%. BRIEF DESCRIPTION OF THE DRAWINGS

[0299] Figure 1 The XRD spectrum of the solid obtained in Comparative Example 2 is shown, with an enlarged view of the portion where anatase-related peaks are present. 98.5% of the obtained particles have a TS-1 structure, while 1.5% are anatase. The pulses are indicated on the y-axis. The 2θ values ​​are shown on the x-axis.

[0300] Figure 2Shown is a Kubelka-Munk plot, based on %R spectra calculated using a UV / VIS / NIR spectrophotometer Lambda 950 with lamp switching point indication and a 150 mm integrating sphere (Ulbrichtkugel) for titanium zeolite-1 (TS-1) powders of Examples 2-4 and Comparative Examples 1 and 2. The Kubelka-Munk transformation (KM) is indicated on the y-axis, while the wavelength in nanometers is shown on the x-axis. The band above 330 nm (in the range of about 330 nm to about 350 nm) indicates the presence of a significant amount of anatase for samples made from tetraethyl orthotitanate with an APHA number > 300.

[0301] Figure 3 Shown is a Kubelka-Munk diagram, based on the %R spectrum calculation, using a UV / VIS / NIR spectrophotometer Lambda 950 with lamp switching point indication and a 150 mm integrating sphere (Ulbrichtkugel) to measure the TiMWW powders of Example 6 and Comparative Example 3. The Kubelka-Munk transformation (KM) is indicated on the y-axis, while the wavelength in nanometers is shown on the x-axis. The inset on the right shows the portion of the image between 0 and 3 on the y-axis in an enlarged manner. The shoulder peak above 330 nm (in the range of about 330 nm to about 350 nm) of Comparative Example 3 indicates that for samples made of tetrabutyl orthotitanate with an APHA number > 300, a certain amount of anatase is present.

[0302] Figure 4 The results from the continuous epoxidation reaction of Example 7.2 are shown, wherein the temperature of the cooling medium is indicated on the y-axis in °C and the run time is indicated on the x-axis in h.

[0303] Figure 5 The results of the continuous epoxidation reaction of Example 7.2 are shown, wherein the selectivity of propylene oxide relative to hydrogen peroxide (S(H2O2) to PO) is determined according to Reference Example 2 and is expressed in % on the y-axis; the run time is expressed in hours on the x-axis.

[0304] Figure 6 A compilation of the results from the continuous epoxidation reactions of Example 7.2 is shown with selectivity and temperature represented in % and °C, respectively, on the y-axis and run time in hours on the x-axis.

[0305] Citations

[0306] -US 2013 / 296159 A1

[0307] -EP 0 712 852 A1

[0308] -Deng-Gao Huang, Xian Zhang, Bao-Hui Chen, Zi-Sheng Chao Catalysis Today 158 (2010) 510–514 - IN 189381A

[0309] - "Betriebsanleitung der Material-Prüfmaschine" manual, version 1.1, compiled by ZwickTechnische Dokumentation, August-Nagel-Strasse 11, D-89079 Ulm, Germany (1999)

[0310] - "Register 1: Betriebsanleitung / Sicherheitshandbuch für die Material-Prüfmaschine Z2.5 / TS1S" Manual, Edition 1.5, December 2001, Zwick GmbH & Co. Technische Dokumentation, August-Nagel-Strasse 11, D-89079 Ulm, Germany

[0311] -US 2007 / 0099299 A1

[0312] - Stallmach et al., Annual Reports on NMR Spectroscopy 2007, Vol. 61, pp. 51-131

[0313] -S.Kolitcheff, E.Jolimaitre, A.Hugon, J.Verstraete, M.Rivallan, PL.Carrette, F.Couenne and M.Tayakout-Fayolle, Catal.Sci.Technol., 2018, 8, page 4537

[0314] - F. Elwinger, P. Pourmand, and I. Furo, J. Phys. Chem. C. 2017, 121, pp. 13757-13764

[0315] -M. Holz, SR Heil and A. Sacco. Phys. Chem. Chem. Phys., 2000, 2, pp. 4740–4742

[0316] -EP 1 122 249A1

[0317] -EP 1 122 249A1

[0318] - WO 2015 / 049327 A1

[0319] -Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, Volume A, Issue 13 (1989) Pages 443-466

Claims

1. A zeolite material of MFI framework type or MWW framework type obtained from a Ti-containing compound and having a framework structure including Si, O and Ti, wherein the APHA color of the Ti-containing compound is ≤300, wherein the Ti-containing compound comprises a Ti-containing alcoholate, wherein the Ti-containing alcoholate is selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds.

2. The zeolite material of MFI framework type or MWW framework type obtained from a Ti-containing compound according to claim 1 and having a framework structure including Si, O and Ti, wherein the Ti-containing alcoholate is selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

3. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 1 or 2, wherein the Ti-containing compound comprises at least 90 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

4. The zeolitic material of the MFI framework type or the MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 3, wherein the Ti-containing compound comprises at least 95 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

5. The zeolitic material of the MFI framework type or the MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 4, wherein the Ti-containing compound comprises at least 96 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

6. The zeolitic material of the MFI framework type or the MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 5, wherein the Ti-containing compound comprises at least 97 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

7. The zeolitic material of the MFI framework type or the MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 6, wherein the Ti-containing compound comprises at least 98 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

8. The zeolitic material of the MFI framework type or the MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 7, wherein the Ti-containing compound comprises at least 99 wt.-% of Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

9. The zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 1, wherein the Ti-containing compound comprises ≤ 10 wt. % of a substance of formula (I), based on the total weight of the Ti-containing compound, Among them, R 1 and R 2 are independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups, R 3 is selected from a hydrogen atom, a branched or unbranched C1 to C6 alkyl group and a branched or unbranched C1 to C6 alkenyl group.

10. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 9, wherein the Ti-containing compound comprises ≤ 5 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

11. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 10, wherein the Ti-containing compound comprises ≤ 4 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

12. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 11, wherein the Ti-containing compound comprises ≤ 3 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

13. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 12, wherein the Ti-containing compound comprises ≤ 2 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

14. A zeolitic material of the MFI framework type or MWW framework type having a framework structure comprising Si, O and Ti obtained from a Ti-containing compound according to claim 13, wherein the Ti-containing compound comprises ≤ 1 wt. % of the substance of formula (I), based on the total weight of the Ti-containing compound.

15. A zeolite material of MFI framework type or MWW framework type obtained from a Ti-containing compound and having a framework structure comprising Si, O and Ti according to claim 9, wherein the substance of formula (I) is selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-dien-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone, 2,6-dimethyl-hept-2,5-dien-4-one) and a mixture of hept-2,5-dien-4-one and 2,6-dimethyl-hept-2,5-dien-4-one.

16. A Ti-containing compound with an APHA color of ≤300, wherein the Ti-containing compound comprises a Ti-containing alcoholate, wherein the Ti-containing alcoholate is selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4), tetra-n-butyl orthotitanate Ti(OBu)4 and a mixture of two or more of these compounds.

17. The Ti-containing compound with an APHA color of ≤300 according to claim 16, wherein the Ti-containing alcoholate is selected from tetraethyl orthotitanate (Ti(OEt)4), tetraisopropyl orthotitanate (Ti(OPr)4) and a mixture of Ti(OEt)4 and Ti(OPr)4.

18. The Ti-containing compound having an APHA color of ≤300 according to claim 16, wherein the Ti-containing compound comprises at least 90 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

19. The Ti-containing compound having an APHA color of ≤300 according to claim 18, wherein the Ti-containing compound comprises at least 95 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

20. The Ti-containing compound having an APHA color of ≤300 according to claim 19, wherein the Ti-containing compound comprises at least 96 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

21. The Ti-containing compound having an APHA color of ≤300 according to claim 20, wherein the Ti-containing compound comprises at least 97 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

22. The Ti-containing compound having an APHA color of ≤300 according to claim 21, wherein the Ti-containing compound comprises at least 98 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

23. The Ti-containing compound having an APHA color of ≤300 according to claim 22, wherein the Ti-containing compound comprises at least 99 wt% of the Ti-containing alcoholate, based on the total weight of the Ti-containing compound.

24. The Ti-containing compound having an APHA color of ≤300 according to any one of claims 16 to 23, wherein the Ti-containing compound comprises ≤10 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound, Among them, R 1 and R 2 are independently selected from hydrogen atoms and branched or unbranched C1 to C6 alkyl groups, R 3 is selected from a hydrogen atom, a branched or unbranched C1 to C6 alkyl group and a branched or unbranched C1 to C6 alkenyl group.

25. The Ti-containing compound having an APHA color of ≤300 according to claim 24, wherein the Ti-containing compound comprises ≤5 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound.

26. The Ti-containing compound having an APHA color of ≤300 according to claim 25, wherein the Ti-containing compound comprises ≤4 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound.

27. The Ti-containing compound having an APHA color of ≤300 according to claim 26, wherein the Ti-containing compound comprises ≤3 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound.

28. The Ti-containing compound having an APHA color of ≤300 according to claim 27, wherein the Ti-containing compound comprises ≤2 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound.

29. The Ti-containing compound having an APHA color of ≤300 according to claim 28, wherein the Ti-containing compound comprises ≤1 wt% of the substance of formula (I), based on the total weight of the Ti-containing compound.

30. The Ti-containing compound having an APHA color of ≤300 according to claim 29, wherein the substance of formula (I) is selected from CH3-CH=CH-C(=O)-CH=CH-CH3 (hept-2,5-dien-4-one), (CH3)2C=CH-C(=O)-CH=C(CH3)2 (phorone=2,6-dimethyl-hept-2,5-dien-4-one) and a mixture of hept-2,5-dien-4-one and 2,6-dimethyl-hept-2,5-dien-4-one.

31. Use of a Ti-containing compound having an APHA color of ≤ 300 according to any one of claims 16 to 30 for preparing a zeolitic material having a framework structure comprising Si, O and Ti according to any one of claims 1 to 15.

32. A method for preparing a zeolite material having a framework structure comprising Si, O and Ti, the method comprising a) preparing a mixture comprising one or more Si sources, one or more Ti-containing compounds and one or more structure directing agents and water, or a') preparing a mixture comprising one or more Si sources, a reaction product from premixing one or more Ti-containing compounds and one or more structure directing agents, and water; b) feeding the mixture prepared in a) or a') into a reactor; and c) crystallizing a zeolitic material having a framework structure comprising Si, O and Ti from the mixture in a reactor, wherein the mixture is heated to a temperature of 70 to 300° C.; The Ti-containing compound has an APHA color of ≤300, wherein the Ti-containing compound is as defined in any one of claims 16 to 30.

33. A molded article comprising the zeolite material having a framework structure comprising Si, O and Ti according to any one of claims 1 to 15.

34. Use of the molding according to claim 33 as adsorbent, absorbent, catalyst or catalyst component.

35. The use according to claim 34, wherein the molding is used as a catalyst or as a catalyst component.

36. The use according to claim 35, wherein the molded article is used as a Lewis acid catalyst or a Lewis acid catalyst component, as an isomerization catalyst or as an isomerization catalyst component, as an oxidation catalyst or as an oxidation catalyst component, as an aldol condensation catalyst or as an aldol condensation catalyst component, or as a Prins reaction catalyst or as a Prins reaction catalyst component.

37. A method of oxidizing an organic compound comprising contacting the organic compound with a catalyst comprising the molded article of claim 33.

38. The method of claim 37, wherein the organic compound is contacted with the catalyst comprising the molded article of claim 33 in a continuous mode.

39. The method according to claim 37, which is used for epoxidizing an organic compound.

40. The process according to claim 39, for epoxidizing an organic compound having at least one CC double bond.

41. The process according to claim 40, which is used for epoxidizing C2-C10 olefins.

42. The process according to claim 41, for epoxidizing C2-C5 olefins.

43. The process according to claim 42, for epoxidizing C2-C4 olefins.

44. The process of claim 43, for epoxidizing C2 or C3 olefins.

45. A process according to claim 44 for epoxidizing propylene.

Citation Information

Patent Citations

  • Improved process for titanium silicalite-catalyzed epoxidation

    EP0712852A1

  • Process for producing oxiranes

    EP1122249A1

  • Improved process for preparation of titanium silicate

    IN189381B

  • Catalyst support, catalyst and process for dehydrogenating hydrocarbons

    US20070099299A1

  • Zeolitic materials and methods for their preparation using alkenyltrialkylammonium compounds

    US20130296159A1